Optical plastic film, optical layered body, polarizing plate and image display device using the same
By controlling the standard deviation σ of the slow axis angle in the plastic film, the rainbow spot and black screen problems caused by polarization elements and stretched plastic film are solved, and the rainbow spot and black screen are suppressed without increasing the in-plane phase difference and without requiring axial alignment, which improves yield and operability.
Patent Information
- Application Number
- CN202310868742.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-03-30
AI Technical Summary
In the prior art, when using polarization elements and stretched plastic films, there are problems of rainbow spots and black screens, and it is necessary to increase in the in-plane phase difference or perform axial alignment to solve these problems, resulting in poor operability and low yield.
By non-uniforming the angle of the slow axis in the plastic film, the standard deviation σ reaches above the specified value, thereby suppressing rainbow spots and black screens without increasing the in-plane phase difference.
It is achieved to suppress rainbow spots when observing naked eyes, and avoid black screen when observing with polarized sunglasses, and does not require axial alignment and improve in-plane phase difference, which improves yield and operability.
Smart Images

Figure CN116879993B_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application with the application date of March 30, 2021, the invention name of "Optical plastic film, and optical layered body, polarizer and image display device using the same", and the application number of 202180035179.2. Technical Field
[0002] The present invention relates to an optical plastic film, and an optical layered body, a polarizing plate and an image display device using the plastic film. Background Art
[0003] Various optical plastic films are often used in optical components such as image display devices. For example, in an image display device having a polarizer on a display element, a plastic film is used to protect a polarizing element constituting the polarizer. In this specification, a "plastic film for protecting a polarizing element" is sometimes referred to as a "polarizing element protective film".
[0004] Plastic films for image display devices, such as polarizer protective films, preferably have excellent mechanical strength. Therefore, as the plastic film for image display devices, it is preferable to use a stretched plastic film.
[0005] When a stretched plastic film is arranged on a polarizing element, the stretched plastic film disturbs the polarization state of the linearly polarized light passing through the polarizing element, so there is a problem that spots of a rainbow pattern are observed. In order to solve this problem, patent documents 1 to 3 are proposed. In this specification, "spots of a rainbow pattern" are sometimes referred to as "rainbow spots".
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2009-300611
[0009] Patent Document 2: Japanese Patent Application Publication No. 2010-244059
[0010] Patent Document 3: Japanese Patent Application Publication No. 2011-107198 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In Patent Documents 1 and 2, the absorption axis of the polarizing element and the slow axis of the stretched plastic film are arranged in parallel or perpendicularly to suppress rainbow spots.
[0013] However, when the polarizing element and the stretched plastic film are arranged in the relationship as in Patent Documents 1 and 2, there is a problem that the screen becomes black when the image display device is viewed through polarized sunglasses. In this specification, this phenomenon is sometimes referred to as "black screen".
[0014] Patent document 3 discloses a liquid crystal display device, which makes the light source of the image display device a specific white light source, so that the in-plane phase difference of the stretched plastic film is as high as 3000nm to 30000nm, and the absorption axis of the polarization element and the slow axis of the stretched plastic film are arranged at approximately 45 degrees, thereby eliminating rainbow spots and black screens.
[0015] However, Patent Document 3 requires the use of a stretched plastic film having a large in-plane phase difference. Furthermore, a stretched plastic film having a large in-plane phase difference is generally stretched in one direction, and thus has problems such as being easily broken in the stretching direction.
[0016] Furthermore, Patent Document 3 requires precise alignment of the absorption axis of the polarizing element and the slow axis of the stretched plastic film in order to suppress black screen, which results in poor operability and difficulty in improving yield.
[0017] The present invention aims to provide an optical plastic film which can suppress rainbow spots when observed with the naked eye and black screens when observed with polarized sunglasses without increasing the in-plane phase difference and without requiring axis alignment; and to provide an optical layered body, a polarizing plate and an image display device using the optical plastic film.
[0018] Means for solving problems
[0019] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by making the standard deviation σ of the slow axis of a plastic film having a reduced in-plane retardation not uniform but equal to or greater than a predetermined value.
[0020] The present invention provides the following optical plastic film, and an optical layered body, a polarizing plate, and an image display device using the plastic film.
[0021] [1] An optical plastic film that satisfies the following conditions 1 and 2.
[0022] <Condition 1>
[0023] A large sample of 200mm×300mm size was cut from the plastic film. The large sample was divided into 30 small samples of 40mm×50mm. The 30mm×40mm area after removing 5mm from the edge of each small sample was subdivided into more than 47,000 areas, and then the in-plane phase difference of each subdivided area was measured. Among the above 30 small samples, the average in-plane phase difference of each measured area showed that the proportion of small samples with a size of more than 50nm and less than 1200nm was more than 50%.
[0024] <Condition 2>
[0025] The 30 small samples were measured for the slow axis angle of each region after each subdivision of the small sample in the same manner as in Condition 1. Among the 30 small samples, the proportion of small samples showing a standard deviation σ calculated from the slow axis angle of each measured region of 0.8 degrees or more was 50% or more.
[0026] [2] An optical layered body comprising the optical plastic film according to [1] above and a functional layer.
[0027] [3] A polarizing plate comprising a polarizing element, a first transparent protective plate arranged on one side of the polarizing element, and a second transparent protective plate arranged on the other side of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate comprises the optical plastic film described in [1] above.
[0028] [4] An image display device comprising a display element and a plastic film disposed on a light emitting surface side of the display element, wherein the plastic film is the optical plastic film according to [1].
[0029] Effects of the Invention
[0030] The optical plastic film of the present invention, and the optical layered body, polarizing plate and image display device using the same can suppress rainbow spots when observed with the naked eye and black screens when observed with polarized sunglasses without increasing the in-plane phase difference. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a plan view for explaining a sample of 40 mm×50 mm in Conditions 1 and 2 and a region of 30 mm×40 mm obtained by removing 5 mm from the edge of the sample.
[0032] Figure 2 The diagram explains a method for sampling a rolled plastic film.
[0033] Figure 3 This is a cross-sectional view showing one embodiment of the image display device of the present invention.
[0034] Figure 4 It is a cross-sectional view showing another embodiment of the image display device of the present invention.
[0035] Figure 5 It is a figure which shows schematically the state of a continuous folding test.
[0036] Figure 6 This is a schematic cross-sectional view of an apparatus for measuring the erosion rate of a plastic film.
[0037] Figure 7 This is an image of a state in which a plastic film is worn away by a test liquid containing pure water and spherical silica ejected from an ejection unit. DETAILED DESCRIPTION
[0038] Embodiments of the present invention will be described below.
[0039] [Plastic film for optical use]
[0040] The optical plastic film of the present invention satisfies the following conditions 1 and 2.
[0041] <Condition 1>
[0042] A large sample of 200mm×300mm size was cut from the plastic film. The large sample was divided into 30 small samples of 40mm×50mm. The 30mm×40mm area after removing 5mm from the edge of each small sample was subdivided into more than 47,000 areas, and then the in-plane phase difference of each subdivided area was measured. Among the above 30 small samples, the average in-plane phase difference of each measured area showed that the proportion of small samples with a size of more than 50nm and less than 1200nm was more than 50%.
[0043] <Condition 2>
[0044] The 30 small samples were measured for the slow axis angle of each region after each subdivision of the small sample in the same manner as in Condition 1. Among the 30 small samples, the proportion of small samples showing a standard deviation σ calculated from the slow axis angle of each measured region of 0.8 degrees or more was 50% or more.
[0045] <About Measurement>
[0046] The large sample of 200 mm×300 mm used in Condition 1 and Condition 2 was cut out from an arbitrary position of the plastic film.
[0047] In Conditions 1 and 2, the large sample was divided into 30 small samples of 40 mm×50 mm, and a 30 mm×40 mm area was measured after removing 5 mm from the edge of each small sample. Figure 1In the figure, the outer quadrilateral area represents a small sample of 40 mm × 50 mm in size, and the inner quadrilateral area represents an area of 30 mm × 40 mm.
[0048] The reason for measuring the area 5 mm removed from the edge of the small sample is considered to be as follows: when cutting the large sample, stress is easily applied to the vicinity of the edge of the plastic film, so the optical axis near the edge of the small sample may be deformed.
[0049] Optical plastic films may be in sheet form or in roll form. For sheet-form plastic films or roll-form plastic films, preferably, a large sample is sampled, 30 small samples are cut out from the large sample, and then conditions 1 and 2 are determined.
[0050] When a plurality of large samples of 200 mm×300 mm in size can be collected from a sheet-like plastic film, it is preferable to perform sampling in a layout that can obtain the largest number of large samples.
[0051] When a plurality of large samples of 200 mm×300 mm in size can be collected from a sheet of plastic film, any large sample only needs to satisfy conditions 1 and 2. In order to more easily exert the effect of the present invention, the proportion of large samples satisfying conditions 1 and 2 in all large samples is preferably 50% or more, more preferably 70% or more, further preferably 90% or more, and further preferably 100%. The same applies to condition 3 described later.
[0052] In the case of a rolled plastic film, it is preferable to determine whether or not conditions 1 and 2 are satisfied in the width direction of each roll as described in the following (1) to (4).
[0053] (1) In the width direction of the rolled plastic film 10b, cut out as many large samples as are available, with the size of 200 mm in the flow direction and 300 mm in the width direction. For example, when the roll width is 1200 mm, cut out 4 large samples. Alternatively, when the roll width is 1600 mm, cut out 5 large samples. When the roll width is 1600 mm, 100 mm is left in the width direction. The cut large samples are designated as S1, S2, ... Sn (see Figure 2 ).
[0054] (2) Thirty small samples of 40 mm × 50 mm are cut out from the large sample S1, and measurements are performed on conditions 1 and 2 to determine whether conditions 1 and 2 are satisfied.
[0055] (3) The various physical properties of a rolled plastic film tend to change in the width direction, but the various physical properties are almost the same in the flow direction. Therefore, when the large sample S1 satisfies conditions 1 and 2, it can be assumed that the parts in the roll that are located in the same width direction as the large sample S1 satisfy conditions 1 and 2 in the entire flow direction of the roll.
[0056] (4) The same operations as those in (2) to (3) above are performed on the large samples S2, ... Sn to determine whether the large samples S2, ... Sn satisfy conditions 1 and 2. Furthermore, for the portion in the roll whose position in the width direction is the same as that of the large sample S2, ... Sn that satisfies conditions 1 and 2, it is assumed that conditions 1 and 2 are satisfied in the entire flow direction of the roll. The same applies to condition 3 described later.
[0057] In conditions 1 and 2, after subdividing the 30mm×40mm area after removing 5mm from the edge of the small sample into more than 47,000 areas, it is necessary to measure the in-plane phase difference and the angle of the slow axis for each subdivided area. If the number of area subdivisions is more than 47,000, the value of the standard deviation σ is sufficiently reliable. Therefore, the number of area subdivisions can be, for example, about 47,000, about 70,000, or about 100,000. Of course, the size of each subdivided area is roughly equal. Such a measurement can be performed using a two-dimensional distribution evaluation device for birefringence, for example.
[0058] As an evaluation device for the two-dimensional distribution of birefringence, there can be cited the trade name "WPA-200-L" of Photonic Lattice Co. When the trade name "WPA-200-L" of Photonic Lattice Co. is used, a small sample is placed on the workbench of the device, and the preview area is adjusted so that the number of pixels in the displayed 30 mm × 40 mm area is 47,000 or more, thereby measuring the in-plane phase difference and the angle of the slow axis of each area divided into 47,000 or more.
[0059] The in-plane phase difference of condition 1 and the phase difference in the thickness direction of condition 3 described later are expressed by the following equations (1) and (2) from the refractive index nx in the slow axis direction, which is the direction in which the refractive index of each measurement position is the largest, the refractive index ny in the fast axis direction, which is the direction orthogonal to the slow axis direction, the refractive index nz in the thickness direction of the plastic film, and the thickness T [nm] of the plastic film. In this specification, the "in-plane phase difference" is sometimes referred to as "Re", and the "phase difference in the thickness direction" is sometimes referred to as "Rth".
[0060] In-plane retardation (Re) = (nx-ny) × T [nm] (1)
[0061] Retardation in the thickness direction (Rth) = ((nx+ny) / 2-nz) × T [nm] (2)
[0062] The optical plastic film of the present invention needs to satisfy the following condition 1.
[0063] <Condition 1>
[0064] A large sample of 200mm×300mm size was cut from the plastic film. The large sample was divided into 30 small samples of 40mm×50mm. The 30mm×40mm area after removing 5mm from the edge of each small sample was subdivided into more than 47,000 areas, and then the in-plane phase difference of each subdivided area was measured. Among the above 30 small samples, the average in-plane phase difference of each measured area showed that the proportion of small samples with a size of more than 50nm and less than 1200nm was more than 50%.
[0065] In this specification, Condition 1 and Condition 2 refer to values at a wavelength of 543 nm.
[0066] When the average in-plane retardation of the plastic film is less than 50 nm, it is difficult to suppress black screen. This is because the plastic film with an average in-plane retardation of less than 50 nm hardly disturbs linearly polarized light and allows the linearly polarized light to pass through as it is.
[0067] On the other hand, when the average value of the in-plane retardation of the plastic film exceeds 1200 nm, rainbow spots cannot be suppressed when observed with the naked eye.
[0068] In addition, even if there are small samples whose average in-plane phase difference is 50 nm or more and 1200 nm or less, if the proportion is less than 50%, it is impossible to suppress black screen or rainbow spots when observed with the naked eye. Among the 30 small samples, the proportion of small samples whose average in-plane phase difference in each measurement area is 50 nm or more and 1200 nm or less is preferably 70% or more, more preferably 90% or more, and further preferably 100%.
[0069] The technique of increasing the in-plane phase difference to 3000 nm or more as in Patent Document 3 cannot suppress rainbow spots when the shape of the spectral spectrum of the image display device is sharp. On the other hand, when the in-plane phase difference is reduced as in the present invention, rainbow spots can be eliminated even if the shape of the spectral spectrum of the image display device is sharp.
[0070] In condition 1, in order to more easily suppress the black screen, the average value of the in-plane phase difference is preferably 100 nm or more, more preferably 150 nm or more, more preferably 200 nm or more, more preferably 250 nm or more, more preferably 300 nm or more, more preferably 400 nm or more, more preferably 520 nm or more, and more preferably 620 nm or more. It should be noted that if the average value of the in-plane phase difference of the plastic film is too small, the standard deviation σ of the angle of the slow axis may become too large. Therefore, from the perspective of making the standard deviation σ of the angle of the slow axis not too large, it is also preferred to make the average value of the in-plane phase difference greater than the specified value.
[0071] In addition, a small in-plane phase difference of the plastic film means that the molecular orientation of the resin constituting the plastic film is insufficient and / or the thickness of the plastic film is thin. Therefore, by making the average value of the in-plane phase difference of the plastic film greater than a specified value, the pencil hardness of the plastic film can be improved. In order to improve the pencil hardness of the plastic film, the average value of the in-plane phase of the plastic film is preferably greater than 100 nm, more preferably greater than 520 nm, and further preferably greater than 620 nm.
[0072] In condition 1, in order to easily suppress rainbow spots when observed with the naked eye, the average value of the in-plane phase difference is preferably 1100nm or less, more preferably 1000nm or less, and more preferably 950nm or less. In addition, if the average value of the in-plane phase difference is large, the bending resistance described later tends to decrease. By making the average value of the in-plane phase difference 950nm or less, the decrease in bending resistance can be easily suppressed.
[0073] When a plurality of upper limit options and lower limit options are shown in the components described in this specification, one selected from the upper limit option and one selected from the lower limit option may be combined as an embodiment of the numerical range.
[0074] For example, in the case of the average value of the above-mentioned in-plane phase difference, 50 nm to 1200 nm, 50 nm to 1100 nm, 50 nm to 1000 nm, 50 nm to 950 nm, 100 nm to 1200 nm, 100 nm to 1100 nm, 100 nm to 1000 nm, 100 nm to 950 nm, 150 nm to 1200 nm, 150 nm to 1100 nm, 150 nm to 1000 nm, 150 nm to 950 nm, 200 nm to 1200 nm, 200 nm to 1100 nm, 200 nm to 1000 nm, 200 nm to 950 nm, 250 nm to 1200 nm, 250 nm to 1100 nm, 0nm or less, 250nm or more and 1000nm or less, 250nm or more and 950nm or less, 300nm or more and 1200nm or less, 300nm or more and 1100nm or less, 300nm or more and 1000nm or less, 300nm or more and 950nm or less, 400nm or more and 1200nm or less, 400nm or more and 1100nm or less, 400nm or more and 1000nm or less, 400nm or more and 950nm or less, 520nm or more and 1200nm or less, 520nm or more and 1100nm or less, 520nm or more and 1000nm or less, 520nm or more and 950nm or less, 620nm or more and 1200nm or less, 620nm or more and 1100nm or less, 620nm or more and 1000nm or less, and 620nm or more and 950nm or less.
[0075] The standard deviation σ of the in-plane phase difference of each subdivided area is not particularly limited, and the lower limit is preferably greater than 5 nm, more preferably greater than 10 nm, more preferably greater than 15 nm, and further preferably greater than 20 nm, and the upper limit is preferably less than 100 nm, more preferably less than 70 nm, and further preferably less than 50 nm.
[0076] As embodiments of the range of the standard deviation σ of the in-plane phase difference, examples include 5 nm and 100 nm, 5 nm and 70 nm, 5 nm and 50 nm, 10 nm and 100 nm, 10 nm and 70 nm, 10 nm and 50 nm, 15 nm and 100 nm, 15 nm and 70 nm, 15 nm and 50 nm, 20 nm and 100 nm, 20 nm and 70 nm, and 20 nm and 50 nm.
[0077] The optical plastic film of the present invention needs to satisfy the following condition 2.
[0078] <Condition 2>
[0079] The 30 small samples were measured for the slow axis angle of each region after each subdivision of the small sample in the same manner as in Condition 1. Among the 30 small samples, the proportion of small samples showing a standard deviation σ calculated from the slow axis angle of each measured region of 0.8 degrees or more was 50% or more.
[0080] The standard deviation σ of the slow axis angle being 0.8 degrees or more indicates that the slow axis of the plastic film has a deviation. When the standard deviation σ is less than 0.8 degrees, the black screen cannot be suppressed.
[0081] In addition, even if there are small samples in which the standard deviation σ of the slow axis angle is greater than 0.8 degrees, when the ratio is less than 50%, the information on the display cannot be read due to a partial black screen. Among the 30 small samples, the ratio of small samples in which the standard deviation σ calculated from the slow axis angle of each measurement area is greater than 0.8 degrees is preferably 70% or more, more preferably 90% or more, and further preferably 100%.
[0082] Conventional optical plastic films are designed so that the direction of the slow axis does not deviate, but the optical plastic film of the present invention intentionally deviates the direction of the slow axis, which is different from the conventional optical film structure. In addition, it can be said that the optical plastic film of the present invention is also characterized by focusing on the deviation of the slow axis in a relatively small area of 30 mm×40 mm.
[0083] Furthermore, from the viewpoint of being able to improve the folding resistance of the plastic film, it is preferable to satisfy condition 2.
[0084] On the other hand, for a general-purpose oriented film with a uniform slow axis, the film breaks after the bending test, or obvious bending marks remain. Specifically, the uniaxially stretched film of Patent Document 3 breaks when the bending test is performed along the slow axis, and obvious bending marks remain when the bending test is performed in a direction perpendicular to the slow axis. In addition, a general-purpose biaxially stretched film has obvious bending marks when the bending test is performed in a direction perpendicular to the slow axis.
[0085] The plastic film of the present invention is preferred in that it is possible to suppress the remaining bending marks or fractures after a bending test regardless of the bending direction.
[0086] In condition 2, the standard deviation σ is preferably 0.9 degrees or more, more preferably 1.0 degrees or more, further preferably 1.2 degrees or more, and further preferably 1.6 degrees or more. By setting the standard deviation σ to 1.6 degrees or more, the effect of suppressing black screen can be extremely improved.
[0087] If the standard deviation σ in condition 2 is too large, the orientation of the plastic film is reduced, the mechanical strength and pencil hardness are reduced, wrinkles are generated under environmental changes, and visibility tends to be adversely affected. Therefore, in condition 2, the standard deviation σ is preferably 20.0 degrees or less, more preferably 15.0 degrees or less, more preferably 10.0 degrees or less, more preferably 7.0 degrees or less, and more preferably 5.0 degrees or less.
[0088] Examples of the range of the standard deviation σ of condition 2 include 0.8 degrees or more, 0.8 degrees or more and 20.0 degrees or less, 0.8 degrees or more and 15.0 degrees or less, 0.8 degrees or more and 10.0 degrees or less, 0.8 degrees or more and 7.0 degrees or less, 0.8 degrees or more and 5.0 degrees or less, 0.9 degrees or more and 20.0 degrees or less, 0.9 degrees or more and 15.0 degrees or less, 0.9 degrees or more and 10.0 degrees or less, 0.9 degrees or more and 7.0 degrees or less, 0.9 degrees or more and 5.0 degrees or less, 1.0 degrees or more and 20.0 degrees or less, 1.0 degrees or more and 1.0 degrees or more. 1.0 degrees to 10.0 degrees, 1.0 degrees to 7.0 degrees, 1.0 degrees to 5.0 degrees, 1.2 degrees to 20.0 degrees, 1.2 degrees to 15.0 degrees, 1.2 degrees to 10.0 degrees, 1.2 degrees to 7.0 degrees, 1.2 degrees to 5.0 degrees, 1.6 degrees to 20.0 degrees, 1.6 degrees to 15.0 degrees, 1.6 degrees to 10.0 degrees, 1.6 degrees to 7.0 degrees, 1.6 degrees to 5.0 degrees.
[0089] The optical plastic film of the present invention preferably satisfies the following condition 2'.
[0090] <Condition 2'>
[0091] The 30 small samples were measured for the slow axis angle of each region after each subdivision of the small sample in the same manner as in Condition 1. Among the 30 small samples, the proportion of small samples having a standard deviation 3σ calculated from the slow axis angle of each measured region of 30.0 degrees or less was 50% or more.
[0092] If the standard deviation 3σ of condition 2' is too large, the orientation of the plastic film may become too low, and the pencil hardness tends to decrease. Therefore, by making the standard deviation 3σ 30.0 degrees or less, the pencil hardness of the plastic film can be easily improved. The standard deviation 3σ is more preferably 25.0 degrees or less, more preferably 20.0 degrees or less, more preferably 15.0 degrees or less, and more preferably 10.0 degrees or less.
[0093] If the standard deviation 3σ of condition 2' is too small, the orientation of the plastic film is too high, and the plastic film may become brittle. Therefore, the standard deviation 3σ is preferably 2.4 degrees or more, more preferably 2.7 degrees or more, more preferably 3.0 degrees or more, more preferably 3.6 degrees or more, and more preferably 4.8 degrees or more.
[0094] Examples of the range of the standard deviation 3σ of the condition 2′ include 2.4 degrees to 30.0 degrees, 2.4 degrees to 25.0 degrees, 2.4 degrees to 20.0 degrees, 2.4 degrees to 15.0 degrees, 2.4 degrees to 10.0 degrees, 2.7 degrees to 30.0 degrees, 2.7 degrees to 25.0 degrees, 2.7 degrees to 20.0 degrees, 2.7 degrees to 15.0 degrees, 2.7 degrees to 10.0 degrees, 3.0 degrees to 30.0 degrees, 3.0 degrees to 25.0 degrees, .0 degrees and below, 3.0 degrees and above 20.0 degrees and below, 3.0 degrees and above 15.0 degrees and below, 3.0 degrees and above 10.0 degrees and below, 3.6 degrees and above 30.0 degrees and below, 3.6 degrees and above 25.0 degrees and below, 3.6 degrees and above 20.0 degrees and below, 3.6 degrees and above 15.0 degrees and below, 3.6 degrees and above 10.0 degrees and below, 4.8 degrees and above 30.0 degrees and below, 4.8 degrees and above 25.0 degrees and below, 4.8 degrees and above 20.0 degrees and below, 4.8 degrees and above 15.0 degrees and below, 4.8 degrees and above 10.0 degrees and below.
[0095] In this specification, the atmosphere for the measurements of conditions 1 and 2, as well as conditions 2', conditions 3 to 6, and other measurements such as total light transmittance, is set to a temperature of 23°C ± 5°C and a relative humidity of 40% to 65%, unless otherwise specified. In addition, the sample is exposed to the above atmosphere for 30 minutes or more before each measurement, unless otherwise specified.
[0096] The optical plastic film of the present invention preferably satisfies the following condition 3.
[0097] <Condition 3>
[0098] The retardation in the thickness direction was measured at the center of the 30 mm×40 mm region for each of the 30 small samples. Among the 30 small samples, the proportion of small samples showing a retardation in the thickness direction of 2000 nm or more was 50% or more.
[0099] In this specification, Condition 3 refers to a value at a wavelength of 589.3 nm.
[0100] By satisfying condition 3, black screen can be easily suppressed not only in the front direction but also when observed from an oblique direction. Among the 30 small samples, the proportion of small samples showing a phase difference of 2000 nm or more in the thickness direction is preferably 70% or more, more preferably 90% or more, and further preferably 100%.
[0101] In condition 3, the retardation in the thickness direction is more preferably 3000 nm or more, further preferably 4000 nm or more, and further preferably 5000 nm or more.
[0102] The upper limit of the retardation in the thickness direction in condition 3 is not particularly limited, but is preferably 15000 nm or less, more preferably 12000 nm or less, and further preferably 9000 nm or less in order to easily satisfy condition 4 described later.
[0103] As implementation examples of the range of the phase difference in the thickness direction of condition 3, there can be cited above 2000nm, above 2000nm and below 15000nm, above 2000nm and below 12000nm, above 2000nm and below 9000nm, above 3000nm and below 15000nm, above 3000nm and below 12000nm, above 3000nm and below 9000nm, above 4000nm and below 15000nm, above 4000nm and below 12000nm, above 4000nm and below 9000nm, above 5000nm and below 15000nm, above 5000nm and below 12000nm, and above 5000nm and below 9000nm.
[0104] The retardation in the thickness direction of condition 3 can be measured using, for example, "RETS-100" manufactured by Otsuka Electronics Co., Ltd.
[0105] When measuring the retardation in the thickness direction or the like using the trade name "RETS-100" manufactured by Otsuka Electronics Co., Ltd., it is preferable to prepare for the measurement in the following procedures (A1) to (A4).
[0106] (A1) First, in order to stabilize the light source of RETS-100, turn on the light source and leave it for more than 60 minutes. Then, select the rotational polarization method and select the θ mode. The θ mode is a mode for angular phase difference measurement and Rth calculation. By selecting this θ mode, the stage is a tilted rotation stage.
[0107] (A2) Next, the following measurement conditions were input into RETS-100.
[0108] (Measurement conditions)
[0109] Delay measurement range: Rotational polarization method
[0110] ·Measurement of spot diameter:
[0111] Tilt angle range: 0°
[0112] ·Measurement wavelength range: 400nm to 800nm
[0113] Average refractive index of the plastic film: For example, in the case of a PET film, N=1.617.
[0114] ·Thickness: Thickness measured separately using SEM
[0115] (A3) Next, no sample is placed in the device to obtain background data. The device is a closed system, and (A1) to (A3) are performed each time the light source is turned on.
[0116] (A4) Then, the sample is placed on a stage in the device and measurement is performed.
[0117] The optical plastic film of the present invention preferably satisfies the following condition 4.
[0118] <Condition 4>
[0119] Among the 30 small samples, the proportion of small samples in which the average value of the in-plane phase difference relative to the phase difference in the thickness direction was 0.20 or less was 50% or more.
[0120] The average value of the above-mentioned in-plane phase difference relative to the phase difference in the thickness direction is "the average value of the above-mentioned in-plane phase difference / the phase difference in the thickness direction". A small average value of the in-plane phase difference / the phase difference in the thickness direction means that the degree of stretching of the optical plastic film is close to equal biaxiality. Therefore, by making the above-mentioned ratio less than 0.20, the mechanical strength and pencil hardness of the plastic film can be easily improved. In addition, it is possible to suppress the plastic film from wrinkling under environmental changes and adversely affecting visibility. Among the 30 small samples, the proportion of small samples showing the above-mentioned ratio of less than 0.20 is preferably 70% or more, more preferably 90% or more, and further preferably 100%.
[0121] The ratio in condition 4 is more preferably 0.17 or less, and further preferably 0.15 or less.
[0122] There is no particular lower limit on the ratio in condition 4. The lower limit on the ratio in condition 4 is usually about 0.01.
[0123] Examples of the range of the ratio in Condition 4 include 0.20 or less, 0.01 or more and 0.20 or less, 0.01 or more and 0.17 or less, and 0.01 or more and 0.15 or less.
[0124] In order to easily obtain the above-mentioned effect brought about by satisfying condition 4, the average value of the in-plane phase difference of condition 1 is preferably 100 nm or more.
[0125] <Condition 5>
[0126] For the 30 small samples, the erosion rate of the plastic film constituting the small sample from the surface to a depth of 20 μm was measured at the center of the 30 mm×40 mm area. The average erosion rate of the plastic film constituting the small sample from the surface to a depth of 20 μm was defined as E 0-20 When, among the above 30 small samples, E 0-20 The proportion of small samples with a particle size of 1.4 μm / g or more was 50% or more.
[0127] In this manual, E 0-20 The measurement was performed under the following measurement conditions.
[0128] <Measurement Conditions>
[0129] Pure water, dispersion liquid and spherical silica with an average particle size within ±8% based on 4.2μm are mixed in a mass ratio of 968:2:30, and the mixed test liquid is stored in a container. The test liquid in the container is sent to the nozzle. Compressed air is sent to the nozzle to accelerate the test liquid in the nozzle, and a specified amount of the test liquid is vertically sprayed from the spray hole at the front end of the nozzle to the plastic film, so that the spherical silica in the test liquid collides with the plastic film. The cross-sectional shape of the nozzle is a 1mm×1mm square, and the distance between the spray hole and the plastic film is 4mm. In addition, the flow rate of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are specified values adjusted by the calibration described later.
[0130] After a predetermined amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped.
[0131] After the spraying of the test liquid was temporarily stopped, the cross-sectional profile of the portion of the plastic film where the spherical silica in the test liquid collided was measured.
[0132] The three steps of ejecting a predetermined amount of the test liquid from the ejection port, temporarily stopping the ejection of the test liquid after ejecting the predetermined amount of the test liquid, and measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid are taken as one cycle, and the above operation is performed until the depth of the cross-sectional profile exceeds 20 μm. Furthermore, in each cycle until the depth of the cross-sectional profile reaches 20 μm, the erosion rate (μm / g) of the plastic film is calculated by dividing the depth (μm) of the cross-sectional profile developed in each cycle by the ejection amount (g) of the test liquid in each cycle. The erosion rate of the plastic film in each cycle until the depth of the cross-sectional profile reaches 20 μm is averaged to calculate the above E 0-20 .
[0133] <Correction>
[0134] The test liquid is stored in the container. The test liquid in the container is delivered to the nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and any amount of the test liquid is vertically sprayed from the spray hole at the front end of the nozzle to the 2 mm thick acrylic plate, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm.
[0135] After spraying an arbitrary amount of the test liquid, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the portion of the acrylic plate where the spherical silica in the test liquid collides is measured.
[0136] The corrosion rate (μm / g) of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the above-mentioned arbitrary amount (g).
[0137] The erosion rate of the acrylic plate is qualified within the range of ±5% based on 1.88 (μm / g). The flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted and calibrated so that the erosion rate of the acrylic plate is within the above range.
[0138] Below, citing Figure 6 The measurement conditions of the erosion rate and the technical meaning of the erosion rate calculated under the above measurement conditions are explained. Figure 6 An example of a device for measuring the erosion rate is MSE-A203, an MSE test device manufactured by Palmeso Co., Ltd.
[0139] In the erosion rate measurement conditions of the present invention, first, pure water, a dispersant, and spherical silica with an average particle size within ±8% based on 4.2 μm are mixed at a mass ratio of 968:2:30, and the mixed test liquid is stored in a container (110). In the container (110), the test liquid is preferably stirred.
[0140] General-purpose pure water can be used as pure water. The resistivity value of pure water is usually 0.1 MΩ·cm or more and 15 MΩ·cm or less.
[0141] The dispersant is not particularly limited as long as it can disperse the spherical silica. Examples of the dispersant include "DEMOL N (Demol N)" produced by Wako Pure Chemical Industries, Ltd. under the trade name.
[0142] In other words, "the average particle size is within ±8% based on 4.2 μm" means that the average particle size is 3.864 μm or more and 4.536 μm or less.
[0143] In the measurement conditions of the erosion rate in this specification, the “average particle size of spherical silica” is measured as a volume average value d50 in a particle size distribution measurement by a laser diffraction method, and refers to a so-called “median diameter”.
[0144] Regarding the above-mentioned spherical silica, in the results of the above-mentioned particle size distribution measurement, when the frequency of the particle size showing the maximum frequency is standardized to 100, the width of the particle size showing a frequency of 50 is preferably within ±10% based on 4.2μm. Regarding the "width of the particle size showing a frequency of 50", "the particle size that is a particle size showing a frequency of 50 and is located in a more positive direction than the particle size showing a frequency of 100 is defined as X", and "the particle size that is a particle size showing a frequency of 50 and is located in a more negative direction than the particle size showing a frequency of 100 is defined as Y", it is represented by "X-Y (μm)". It should be noted that in this specification, the "width of the particle size showing a frequency of 50" is sometimes referred to as the "full width at half maximum of the particle size distribution".
[0145] As spherical silica having an average particle size within ±8% of 4.2 μm, the model "MSE-BS-5-3" designated by Palmeso Co., Ltd. can be cited. As spherical silica that conforms to the model "MSE-BS-5-3" designated by Palmeso Co., Ltd., for example, the part number "BS5-3" of Potters Ballotini Co., Ltd. can be cited.
[0146] The test liquid in the container is sent to the nozzle (510). The test liquid can be sent to the nozzle through the test liquid pipe (210), for example. A flow meter (310) for measuring the flow rate of the test liquid is preferably arranged between the container (110) and the nozzle (510). The flow rate of the test liquid is a value adjusted by the above calibration.
[0147] It should be noted that Figure 6 In the embodiment, the nozzle (510) is arranged in a shell (520) constituting the injection part (500).
[0148] Compressed air is delivered to the nozzle (510). The compressed air is delivered to the nozzle, for example, through a compressed air pipe (220). In the nozzle, the compressed air is preferably delivered to an upstream side relative to a position where the test liquid is delivered. The upstream side refers to a side away from the injection hole of the nozzle.
[0149] Before the compressed air reaches the nozzle (510), a flow meter (320) for measuring the flow rate of the compressed air and a pressure gauge (420) for measuring the pressure of the compressed air are preferably arranged. The compressed air can be supplied by an air compressor (not shown) or the like.
[0150] The flow rate and pressure of the compressed air are the values adjusted by the above calibration.
[0151] When compressed air is supplied to the nozzle (510), the test liquid is accelerated while being mixed with the compressed air. The accelerated test liquid is ejected from the ejection hole at the front end of the nozzle (510) and collides vertically with the plastic film (10). The plastic film is worn mainly by the spherical silica particles in the test liquid.
[0152] It should be noted that a pressure gauge (410) for measuring the pressure of the test liquid in the nozzle is preferably disposed in the nozzle (510). The pressure gauge (410) is preferably located downstream of the position where the compressed air is fed and the position where the test liquid is fed.
[0153] The pressure of the test fluid in the nozzle (510) is a value adjusted by the above-mentioned calibration.
[0154] The test liquid sprayed from the spray hole at the front end of the nozzle (510) is mixed with air and sprayed in a mist form. Therefore, the collision pressure of the spherical silica particles on the plastic film can be reduced. As a result, the amount of wear on the plastic film caused by one spherical silica particle can be suppressed to a trace amount. Figure 7 This is an image showing a state in which a plastic film (10) is worn away by a test liquid containing pure water (A1) and spherical silica (A2) ejected from an ejection unit (500). Figure 7 In the figure, symbol A3 represents air, and symbol A4 represents the worn plastic film.
[0155] In addition, since the test liquid contains water with excellent cooling effect, deformation and deterioration of the plastic film caused by heat during collision can be substantially eliminated. In other words, abnormal wear of the plastic film can be substantially eliminated. In addition, water also has the function of cleaning the surface of the worn plastic film and achieving stable wear. In addition, water has the function of accelerating the spherical silica particles or controlling the fluidity of the test liquid.
[0156] In addition, since a large amount of spherical silica collides with the plastic film, the influence of subtle differences in physical properties of individual spherical silica particles can be eliminated.
[0157] Furthermore, regarding the measurement conditions of the present invention, the flow rate of the test liquid supplied to the nozzle, the flow rate of the compressed air supplied to the nozzle, the pressure of the compressed air supplied to the nozzle, and the pressure of the test liquid in the nozzle are set to the values adjusted by the above calibration, and the cross-sectional shape of the nozzle is specified as a 1 mm × 1 mm square, and the distance between the injection hole and the plastic film is specified as 4 mm, thereby specifying the factors that affect the wear amount of the plastic film. It should be noted that the above distance is Figure 6 The distance indicated by "d" refers to the vertical distance between the front end of the nozzle, i.e., the injection hole, and the plastic film.
[0158] From the above results, it can be said that the measurement conditions of the present invention are measurement conditions that can form statistically stable wear marks on the plastic film.
[0159] The plastic film (10) can be mounted on the sample mounting table (810) of the measuring device (900). It should be noted that it is preferred to prepare a laminated body in which the plastic film is bonded to a support (820) such as a stainless steel plate, and to mount the laminated body on the sample mounting table (810).
[0160] The test liquid sprayed onto the plastic film (10) is preferably recovered by a receiver (120) and returned to the container (110) through a return pipe (230).
[0161] The measurement conditions of the present invention include: temporarily stopping the spraying of the test liquid after spraying a predetermined amount of the test liquid; and measuring the cross-sectional profile of the portion of the plastic film where the spherical silica in the test liquid collides after temporarily stopping the spraying of the test liquid.
[0162] The cross-sectional profile refers to the cross-sectional shape of the plastic film worn by the test fluid. The plastic film is worn mainly by the spherical silica particles in the test fluid.
[0163] The cross-sectional profile can be measured by a cross-sectional profile acquisition unit (600) such as a stylus-type surface shape measurement device or a laser interference-type surface shape measurement device. It should be noted that the cross-sectional profile acquisition unit (600) is usually arranged at a position away from the plastic film (10) when the test liquid is sprayed. Therefore, it is preferred that at least one of the plastic film (10) and the cross-sectional profile acquisition unit (600) is movable.
[0164] In the MSE test device of Palmeso Co., Ltd., part number "MSE-A203", the cross-sectional profile is measured by a stylus type.
[0165] Furthermore, in the measurement conditions of the present invention, the three steps of ejecting a specified amount of test liquid from the ejection port, temporarily stopping the ejection of the test liquid after ejecting the specified amount of test liquid, and measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid are taken as one cycle, and the operation is performed until the depth of the cross-sectional profile exceeds 20 μm.
[0166] By performing the above operation, the erosion rate of the plastic film in each cycle can be measured, and further, the variation in the erosion rate of the plastic film can be calculated.
[0167] The above cycle can be continued even after the depth of the cross-sectional profile exceeds 20 μm, but it is preferably terminated when the depth of the cross-sectional profile exceeds 20 μm. In addition, the reason for measuring "from the surface to a depth of 20 μm of the plastic film" is believed to be that the physical properties of the plastic film tend to change easily near the surface and tend to be more stable toward the inside.
[0168] In this specification, the erosion rate of each cycle can be expressed by the following [Formula 1].
[0169] Erosion rate of each cycle (μm / g) = Depth of cross-sectional profile developed in each cycle (μm) / Spray amount of test fluid in each cycle (g) [Formula 1]
[0170] In Formula 1, "the depth (μm) of the cross-sectional profile developed in each cycle" refers to the value represented by "y-x" when the depth of the cross-sectional profile of the nth cycle is defined as x (μm) and the depth of the cross-sectional profile of the n+1th cycle is defined as y (μm). In addition, for the first cycle, the depth (μm) of the cross-sectional profile of the first cycle is equivalent to the "depth (μm) of the cross-sectional profile developed in each cycle".
[0171] It should be noted that, in this specification, the depth of the cross-sectional profile at the n-th cycle refers to the depth of the deepest position of the cross-sectional profile at the n-th cycle. n is an integer greater than or equal to 1.
[0172] In Formula 1, "the injection amount (g) of the test liquid in each cycle" is fixed in principle, but may vary slightly in each cycle.
[0173] The injection amount of the test liquid in each cycle is not particularly limited, but the lower limit is preferably 0.5 g or more, more preferably 1.0 g or more, and the upper limit is preferably 3.0 g or less, more preferably 2.0 g or less.
[0174] In the measurement conditions of the present invention, the erosion rate (μm / g) is calculated in each cycle until the depth of the cross-sectional profile reaches 20 μm. Furthermore, the erosion rate in each cycle until the depth of the cross-sectional profile reaches 20 μm is averaged to calculate E 0-20 .
[0175] The above cycle is carried out until the depth of the cross-sectional profile exceeds 20 μm. The data of the cycle in which the depth of the cross-sectional profile exceeds 20 μm is calculated from E 0-20 removed from the data.
[0176] Generally speaking, a plastic film is easily damaged when it is soft, but is not easily damaged when it is hard. The present inventors have studied using the values obtained by evaluating the Martens hardness, indentation hardness, elastic recovery work, etc. using a PICODENRTOR including the depth direction as indices of pencil hardness. However, the parameters such as the Martens hardness, indentation hardness, and elastic recovery work cannot be used as indices of pencil hardness.
[0177] In addition, the strength of plastic films tends to increase when stretched. Specifically, uniaxially stretched plastic films tend to have better pencil hardness than unstretched plastic films, and biaxially stretched plastic films tend to have better pencil hardness than uniaxially stretched plastic films. However, even biaxially stretched plastic films sometimes have insufficient pencil hardness.
[0178] The inventors studied the erosion rate as an index of the pencil hardness of plastic films. As described above, plastic films are easily damaged when they are soft and are not easily damaged when they are hard, so it is believed that a small erosion rate can improve the pencil hardness. However, the inventors found that, on the contrary, by increasing the erosion rate E 0-20 The present inventors have found that the erosion rate of a biaxially stretched plastic film is higher than that of a uniaxially stretched plastic film, and that the quality of the pencil hardness of a biaxially stretched plastic film can be determined by the erosion rate.
[0179] It should be noted that, as described above, the molecular orientation of the resin constituting the plastic film also affects the pencil hardness of the plastic film. In addition, the plastic film tends to have good mechanical strength such as pencil hardness when σ and 3σ are not too large.
[0180] The reason why the erosion rate of the plastic film is related to the pencil hardness is considered to be as follows.
[0181] As described above, in the measurement conditions of the present invention, the test solution containing water and spherical silica is mixed with air and sprayed in a mist state. Therefore, the collision pressure of spherical silica particles on the plastic film is suppressed to be relatively low. Thus, it is believed that when the plastic film is soft, the stress when spherical silica collides with the plastic film is easily dispersed, so the plastic film is not easy to wear, and the erosion rate is reduced. On the other hand, when the plastic film is hard, since the stress when spherical silica collides with the plastic film is difficult to be dispersed, it is believed that the plastic film is easy to wear, and the erosion rate increases.
[0182] In addition, it is believed that the difference in the erosion rate in the biaxially stretched plastic film is caused by the difference in the elongation of the molecular chain and the difference in the molecular orientation. For example, in principle, the molecules of the biaxially stretched plastic film are stretched in the plane, but there are also molecules that are not fully stretched locally in the plane. In this way, it is believed that if the proportion of molecules that are not fully stretched locally in the plane increases, the biaxially stretched plastic film becomes locally soft and the erosion rate decreases. In addition, it is believed that even biaxially stretched plastic films with the same in-plane phase difference will show different erosion rates due to different local molecular orientations.
[0183] In the 30 small samples, E 0-20 The ratio of small samples having a particle size of 1.4 μm / g or more is preferably 70% or more, more preferably 90% or more, and even more preferably 100%.
[0184] In condition 5, in order to further improve the pencil hardness, the E 0-20 More preferably, it is 1.6 μm / g or more, more preferably, it is 1.8 μm / g or more, more preferably, it is 1.9 μm / g or more, and more preferably, it is 2.0 μm / g or more.
[0185] In order to make the plastic film not easy to break, E 0-20 It is preferably 3.0 μm / g or less, more preferably 2.5 μm / g or less, and even more preferably 2.2 μm / g or less.
[0186] E 0-20Embodiments of the preferred numerical range of can include, for example, 1.4 μm / g to 3.0 μm / g, 1.4 μm / g to 2.5 μm / g, 1.4 μm / g to 2.2 μm / g, 1.6 μm / g to 3.0 μm / g, 1.6 μm / g to 2.5 μm / g, 1.6 μm / g to 2.2 μm / g, 1.8 μm / g to 3.0 μm / g, 1.8μm / g or more and 2.5μm / g or less, 1.8μm / g or more and 2.2μm / g or less, 1.9μm / g or more and 3.0μm / g or less, 1.9μm / g or more and 2.5μm / g or less, 1.9μm / g or more and 2.2μm / g or less, 2.0μm / g or more and 3.0μm / g or less, 2.0μm / g or more and 2.5μm / g or less, 2.0μm / g or more and 2.2μm / g or less.
[0187] Before measuring the above erosion rate, the above correction is performed.
[0188] For example, the correction can be performed as follows.
[0189] <Correction>
[0190] The test liquid is stored in the container. The test liquid in the container is delivered to the nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and any amount of the test liquid is vertically sprayed from the spray hole at the front end of the nozzle to the acrylic plate with a thickness of 2 mm, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm.
[0191] After spraying an arbitrary amount of the test liquid, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the portion of the acrylic plate where the spherical silica in the test liquid collides is measured.
[0192] The corrosion rate (μm / g) of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the above-mentioned arbitrary amount (g).
[0193] The erosion rate of the acrylic plate is qualified within the range of ±5% based on 1.88 (μm / g). The flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted and calibrated so that the erosion rate of the acrylic plate is within the above range.
[0194] The test solution used in the calibration is the same as the test solution used in the measurement conditions to be performed later.
[0195] In addition, the measuring device used for calibration is the same as the measuring device used in the measurement conditions to be performed later.
[0196] The difference between the calibration and the measurement conditions to be performed later is that, for example, an acrylic plate with a thickness of 2 mm as a standard sample is used as a sample in the calibration, while a plastic film is used as a sample in the measurement conditions.
[0197] The acrylic plate with a thickness of 2 mm as the standard sample is preferably a polymethyl methacrylate plate. In addition, the acrylic plate with a thickness of 2 mm as the standard sample is preferably, when the average value of the erosion rate of the acrylic plate measured under the following measurement condition A is defined as AcE, AcE is 1.786 μm / g or more and 1.974 μm / g or less. In addition, as the spherical silica in the following measurement condition A, the model "MSE-BS-5-3" specified by Palmeso Co., Ltd. can be cited. As a spherical silica that meets the model "MSE-BS-5-3" specified by Palmeso Co., Ltd., for example, the part number "BS5-3" of Potters Ballotini Co., Ltd. can be cited.
[0198] <Measurement Condition A>
[0199] Pure water, dispersant and spherical silica with an average particle size within ±8% based on 4.2 μm are mixed in a mass ratio of 968:2:30, and the mixed test liquid is stored in a container. The test liquid in the container is sent to the nozzle. Compressed air is sent to the nozzle to accelerate the test liquid in the nozzle, and a specified amount of the test liquid is vertically sprayed from the spray hole at the front end of the nozzle to the acrylic plate, so that the spherical silica in the test liquid collides with the acrylic. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic is 4 mm. In addition, with respect to the flow rates of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle, the flow rate of the test liquid is greater than 100 ml / min and less than 150 ml / min, the flow rate of the compressed air is greater than 4.96 L / min and less than 7.44 L / min, the pressure of the compressed air is greater than 0.184 MPa and less than 0.277 MPa, and the pressure of the test liquid in the nozzle is greater than 0.169 MPa and less than 0.254 MPa.
[0200] After 4 g of the test liquid was sprayed, the spraying of the test liquid was temporarily stopped.
[0201] After the spraying of the test liquid was temporarily stopped, the cross-sectional profile of the portion of the acrylic plate where the spherical silica in the test liquid collided was measured.
[0202] Then, the erosion rate AcE of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the spraying amount of the test liquid 4 g. The unit of AcE is "μm / g".
[0203] During the calibration, the erosion rate of the acrylic plate is qualified within the range of ±5% based on 1.88 (μm / g). In order to keep the erosion rate of the acrylic plate within the above range, the flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted.
[0204] In other words, "the erosion rate is ±5% based on 1.88 (μm / g)" means that the erosion rate is 1.786 (μm / g) or more and 1.974 (μm / g) or less.
[0205] <Condition 6>
[0206] For the 30 small samples, the erosion rate of the plastic film constituting the small sample from the surface to a depth of 20 μm was measured at the center of the 30 mm × 40 mm area. The deviation of the erosion rate calculated from the erosion rate of the plastic film constituting the small sample from the surface to a depth of 20 μm was defined as σ 0-20 When , in the above 30 small samples, σ 0-20 / E 0-20 The proportion of small samples with a value of 0.100 or less was 50% or more.
[0207] In this specification, σ 0-20 The erosion rate can be calculated from the erosion rate in each cycle until the depth of the cross-sectional profile reaches 20 μm under the above-mentioned measurement conditions.
[0208] σ 0-20 / E 0-20 represents the coefficient of variation of the erosion rate, σ 0-20 / E 0-20 Small means that the erosion rate is less likely to change in the thickness direction of the plastic film. 0-20 / E 0-20 When the value is 0.100 or less, the erosion rate in the thickness direction is stabilized, and the pencil hardness can be easily further improved.
[0209] In addition, by making σ 0-20 / E 0-20When the thickness of the plastic film is less than 0.100, the film quality of the plastic film can be made homogeneous in the thickness direction. The homogeneity of the film quality of the plastic film in the thickness direction is related to the homogeneity of the film quality of the plastic film itself. When the homogeneity of the film quality of the plastic film in the thickness direction is low, it is sometimes difficult to stably form a functional layer on the plastic film. Therefore, by satisfying condition 6, the quality of the optical layered body having a functional layer on the plastic film can be easily improved.
[0210] In the 30 small samples, σ 0-20 / E 0-20 The ratio of small samples with a molecular weight of 0.100 or less is preferably 70% or more, more preferably 90% or more, and even more preferably 100%.
[0211] In condition 6, σ 0-20 / E 0-20 The upper limit of is more preferably 0.080 or less, further preferably 0.070 or less, further preferably 0.060 or less, further preferably 0.055 or less.
[0212] σ 0-20 / E 0-20 The smaller the value of , the more homogeneous the film quality in the thickness direction of the plastic film. When the film quality in the thickness direction of the plastic film is homogeneous, stress tends to propagate easily in the thickness direction. Therefore, σ 0-20 / E 0-20 It is preferably 0.020 or more, and more preferably 0.035 or more.
[0213] σ 0-20 / E 0-20 Embodiments of the preferred numerical range can include, for example, 0.020 to 0.100, 0.020 to 0.080, 0.020 to 0.070, 0.020 to 0.060, 0.020 to 0.055, 0.035 to 0.100, 0.035 to 0.080, 0.035 to 0.070, 0.035 to 0.060, and 0.035 to 0.055.
[0214] In order to make the erosion rate of the plastic film within the above range, it is preferable to uniformly stretch the molecules within the surface of the plastic film.
[0215] Plastic films can be produced, for example, by general stepwise biaxial stretching. In the stretching in the flow direction of stepwise biaxial stretching, if the stretching time is shortened, the erosion rate tends to decrease, and if the stretching time is prolonged, the erosion rate tends to increase. The reason is believed to be that if the stretching time is short, it is difficult for the molecules in the surface of the plastic film to stretch evenly, while if the stretching time is long, it is easy for the molecules in the surface of the plastic film to stretch evenly. That is, in order to make E 0-20It is preferable to prolong the stretching time. Furthermore, by appropriately increasing the stretching ratio to a degree of physical property imbalance and prolonging the stretching time, it is possible to more easily make E 0-20 It is 1.4 μm / g or more.
[0216] <Relationship between the width direction of plastic film and the slow axis>
[0217] The optical plastic film preferably has high orientation in the entire width direction. The state in which the plastic film has high orientation in the entire width direction means that in a plastic film with a width of 1000 mm, the vibration amplitude of the slow axis in the entire width direction is 24.0 degrees or less. The vibration amplitude refers to the value of half the difference between the minimum and maximum values of the angle of the slow axis in the entire width direction.
[0218] For a common biaxially stretched optical plastic film such as PET with a thickness of 15 μm to 100 μm, the vibration amplitude of the slow axis in the entire width direction of the plastic film increases due to the bowing phenomenon. Specifically, the vibration amplitude of the slow axis in the entire width direction of a common biaxially stretched optical plastic film with a width of 1000 mm is close to 30.0 degrees. (Condition 2 of the optical plastic film of the present invention specifies the deviation of the slow axis in a small area of 30 mm × 40 mm. On the other hand, the vibration amplitude of the slow axis in the entire width direction of the above-mentioned plastic film specifies the vibration amplitude of the slow axis in a large area, which is different in this point.)
[0219] By setting the vibration amplitude of the slow axis in the entire width direction of the plastic film to 24.0 degrees or less, it is possible to easily suppress the variation of physical properties such as pencil hardness in the width direction of the plastic film. The vibration amplitude is more preferably 20.0 degrees or less, and even more preferably 17.0 degrees or less.
[0220] It should be noted that if the vibration amplitude is too small, the plastic film may not be sufficiently biaxially stretched. Therefore, the vibration amplitude is preferably 4.0 degrees or more, more preferably 6.0 degrees or more, and even more preferably 8.0 degrees or more.
[0221] The slope of the slow axis of the optical plastic film relative to the width direction or the flow direction is preferably 24.0 degrees or less, more preferably 20.0 degrees or less. When cutting a quadrilateral plastic film from a large plastic film, it is mostly cut along the width direction and the flow direction of the large plastic film. The smaller the slope of the slow axis of the plastic film relative to the width direction, the smaller the difference between the width direction of the cut plastic film and the slow axis direction of the plastic film, so it is easy to stabilize the optical properties of the optical plastic film when it is applied to an image display device. It should be noted that in order to easily suppress black screens, a technology for increasing the slope of the slow axis of the plastic film relative to the width direction has also been studied. However, the optical plastic film of the present invention can suppress black screens by satisfying condition 2, so there is no need to increase the slope of the slow axis of the plastic film relative to the width direction.
[0222] The slow axis of the plastic film can be measured as "orientation angle (degrees)" in, for example, "RETS-100" manufactured by Otsuka Electronics Co., Ltd.
[0223] <Plastic film>
[0224] The laminated structure of the plastic film may be a single-layer structure or a multi-layer structure, of which a single-layer structure is preferred.
[0225] In order to improve mechanical strength and suppress rainbow spots, the plastic film is preferably a stretched plastic film with a small in-plane phase difference. In addition, in order to reduce the in-plane phase difference of the stretched plastic film, it is important to perform fine stretching control such as making the stretching in the flow direction and the width direction evenly close. The physical properties in the thickness direction of the single-layer structure are roughly uniform, and it is easier to perform fine stretching control than a multi-layer structure, so it is preferred from this point of view.
[0226] As the resin component constituting the plastic film, polyester, triacetyl cellulose (TAC), cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyether sulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, polymethyl methacrylate, polycarbonate, polyurethane and amorphous olefin (Cyclo-Olefin-Polymer (cycloolefin polymer): COP) etc. can be cited. Among these, polyester is preferred from the aspect of easy improvement of mechanical strength and pencil hardness. That is, the optical plastic film is preferably a polyester film.
[0227] As described above, the polyester film can be easily improved in pencil hardness and the like, and thus can be suitably used as a surface material for an image display device.
[0228] On the other hand, most polycarbonate films and amorphous olefin films have a low pencil hardness of B or less. Therefore, in order to improve the pencil hardness of polycarbonate films and amorphous olefin films, efforts need to be made to increase the film thickness, provide a very thick functional layer, or further cover with a sputtering film. Thus, polycarbonate films and amorphous olefin films have disadvantages such as thicker films when the pencil hardness is increased, and therefore are difficult to use as surface materials for image display devices.
[0229] In addition, the following study was conducted: by using a resin that easily imparts optical isotropy, such as triacetyl cellulose, cycloolefin resin, and polymethyl methacrylate, as a resin constituting the plastic film, the in-plane phase difference can be made infinitely small even when the plastic film is stretched. However, it is difficult to control the production conditions of the stretched plastic film using triacetyl cellulose, cycloolefin resin, and polymethyl methacrylate, and therefore it tends to be difficult to adjust the optical properties such as the in-plane phase difference and the deviation range of the slow axis to the preferred range of the optical properties of the optical plastic film of the present invention.
[0230] Examples of the polyester constituting the polyester film include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc. Among these, PET is preferred because it has low intrinsic birefringence and is easy to reduce in-plane phase difference.
[0231] The plastic film may also contain additives such as ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, anti-gelling agents and surfactants.
[0232] In order to improve the mechanical strength, the thickness of the plastic film is preferably 10 μm or more, more preferably 20 μm or more, further preferably 25 μm or more, and further preferably 30 μm or more.
[0233] In order to easily satisfy condition 1 and improve the bending resistance, the thickness of the plastic film is preferably 75 μm or less, more preferably 60 μm or less, further preferably 55 μm or less, and further preferably 50 μm or less.
[0234] As an embodiment of the thickness range of the plastic film, there can be cited 10 μm to 75 μm, 10 μm to 60 μm, 10 μm to 55 μm, 10 μm to 50 μm, 20 μm to 75 μm, 20 μm to 60 μm, 20 μm to 55 μm, 20 μm to 50 μm, 25 μm to 75 μm, 25 μm to 60 μm, 25 μm to 55 μm, 25 μm to 50 μm, 30 μm to 75 μm, 30 μm to 60 μm, 30 μm to 55 μm, 30 μm to 50 μm.
[0235] The haze of the optical plastic film in JIS K7136:2000 is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably 1.0% or less.
[0236] The total light transmittance of the optical plastic film according to JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.
[0237] In order to improve mechanical strength and pencil hardness, the plastic film is preferably a stretched plastic film, more preferably a stretched polyester film. In addition, the stretched polyester film is more preferably a single-layer structure of a polyester resin layer.
[0238] The stretched plastic film can be obtained by stretching a resin layer containing components constituting the plastic film. The stretching method can include biaxial stretching such as stepwise biaxial stretching and synchronous biaxial stretching, and uniaxial stretching such as longitudinal uniaxial stretching. Among these, biaxial stretching that is easy to reduce the in-plane phase difference and easy to improve the mechanical strength and pencil hardness is preferred. That is, the stretched plastic film is preferably a biaxially stretched plastic film. Among the biaxially stretched plastic films, a biaxially stretched polyester film is preferred, and a biaxially stretched polyethylene terephthalate film is more preferred.
[0239] -Gradually bi-directional stretching-
[0240] In stepwise biaxial stretching, the cast film is stretched in the flow direction and then stretched in the width direction of the film.
[0241] The stretching in the flow direction is usually implemented by the circumferential speed difference of the stretching roller, and can be carried out in one stage, or multiple stretching rollers can be used to carry out in multiple stages. In order to suppress the excessive deviation of optical characteristics such as in-plane phase difference, it is preferred to make multiple nip rollers close to the stretching roller. The stretching ratio in the flow direction is usually more than 2 times and less than 15 times, and in order to suppress the excessive deviation of optical characteristics such as in-plane phase difference, it is preferably more than 2 times and less than 7 times, more preferably more than 3 times and less than 5 times, and further preferably more than 3 times and less than 4 times.
[0242] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature is preferably higher than the glass transition temperature of the resin and lower than the glass transition temperature + 100°C. In the case of PET, it is preferably higher than 70°C and lower than 120°C, more preferably higher than 80°C and lower than 110°C, and further preferably higher than 95°C and lower than 110°C. By rapidly increasing the temperature of the film and shortening the stretching interval at low temperature, the average value of the in-plane phase difference tends to become smaller.
[0243] When heating during stretching or cooling after stretching, it is preferred to blow wind containing turbulence to the film. By blowing wind containing turbulence, a temperature difference is generated in a small area within the film surface, and the orientation axis is easily slightly offset due to the above temperature difference, so condition 2 can be easily satisfied.
[0244] In-line coating can be used to impart lubricity, adhesion, antistatic properties, and other functions to the film stretched in the flow direction. In addition, surface treatments such as corona treatment, flame treatment, and plasma treatment can be performed as needed before in-line coating.
[0245] The coating film formed in the inline coating is extremely thin, about 10 nm to 2000 nm. The coating film is stretched to be thinner by stretching. In this specification, such thin layers are not counted as the number of layers constituting the plastic film.
[0246] About the stretching in the width direction, usually, a tenter method is used, and the two ends of the film are held by a clamp while being transmitted, and stretched in the width direction. The stretching ratio in the width direction is usually more than 2 times and less than 15 times. In order to suppress the excessive deviation of optical properties such as in-plane phase difference, the stretching ratio in the width direction is preferably more than 2 times and less than 5 times, more preferably more than 3 times and less than 5 times, and more preferably more than 3 times and less than 4.5 times. In addition, compared to the longitudinal stretching ratio, it is more preferred to increase the width stretching ratio.
[0247] The stretching temperature is preferably not less than the glass transition temperature of the resin and not more than the glass transition temperature + 120°C, and the temperature preferably increases from the upstream to the downstream. Specifically, when the stretching zone in the width direction is divided into two parts, the difference between the upstream temperature and the downstream temperature is preferably not less than 20°C, more preferably not less than 30°C, further preferably not less than 35°C, and further preferably not less than 40°C. In the case of PET, the first stage stretching temperature is preferably not less than 80°C and not more than 120°C, more preferably not less than 90°C and not more than 110°C, and further preferably not less than 95°C and not more than 105°C.
[0248] For the plastic film which has been subjected to stepwise biaxial stretching as described above, it is preferred to perform heat treatment in a tenter at a temperature above the stretching temperature and below the melting point in order to impart flatness and dimensional stability. Specifically, in the case of PET, it is preferred to perform heat fixation at a temperature in the range of 150°C to 255°C, more preferably 200°C to 250°C. In addition, in order to suppress excessive deviation of optical properties such as in-plane phase difference, it is preferred to perform additional stretching of 1% to 10% in the first half of the heat treatment.
[0249] After the stepwise biaxial stretching and before the above-mentioned heat treatment, the plastic film is preferably cooled by wind containing turbulence. Through the above-mentioned cooling process, a temperature difference is generated in a small area within the film surface, and the orientation axis is easily slightly offset due to the above-mentioned temperature difference, so that condition 2 can be easily satisfied.
[0250] After the plastic film is heat-treated, it is slowly cooled to room temperature and then rolled up. In addition, as needed, relaxation treatment can be used in combination during heat treatment or slow cooling. In order to suppress excessive deviations of optical properties such as in-plane phase difference, the relaxation rate during heat treatment is preferably 0.5% to 5%, more preferably 0.5% to 3%, more preferably 0.8% to 2.5%, and more preferably 1% to 2%. In addition, in order to suppress excessive deviations of optical properties such as in-plane phase difference, the relaxation rate during slow cooling is preferably 0.5% to 3%, more preferably 0.5% to 2%, more preferably 0.5% to 1.5%, and more preferably 0.5% to 1.0%. In order to improve planarity, the temperature during slow cooling is preferably 80°C to 150°C, more preferably 90°C to 130°C, more preferably 100°C to 130°C, and more preferably 100°C to 120°C.
[0251] -Synchronous bidirectional stretching-
[0252] In synchronous biaxial stretching, the cast film is introduced into a synchronous twin-screw tenter, and the film is conveyed while being held at both ends by a clamp, and is stretched synchronously and / or stepwise in the flow direction and the width direction. Synchronous biaxial stretching machines include a pantograph type, a screw type, a drive motor type, and a linear motor type, but a drive motor type or a linear motor type that can arbitrarily change the stretch ratio and can perform relaxation treatment at any location is preferred.
[0253] The ratio of simultaneous biaxial stretching is usually 6 times to 50 times in terms of area ratio. In order to suppress excessive deviation of optical properties such as in-plane phase difference, it is preferably 8 times to 30 times, more preferably 9 times to 25 times, further preferably 9 times to 20 times, and further preferably 10 times to 15 times.
[0254] In the case of simultaneous biaxial stretching, in order to suppress the orientation difference within the plane, it is preferred that the stretching ratios in the flow direction and the width direction be the same and the stretching speeds be substantially the same.
[0255] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature of the simultaneous biaxial stretching is preferably not less than the glass transition temperature of the resin and not more than glass transition temperature + 120°C. In the case of PET, it is preferably not less than 80°C and not more than 160°C, more preferably not less than 90°C and not more than 150°C, and further preferably not less than 100°C and not more than 140°C.
[0256] The film subjected to simultaneous biaxial stretching is preferably subjected to heat treatment at a temperature above the stretching temperature and below the melting point in a heat fixation chamber in a tenter in order to impart flatness and dimensional stability. The conditions for the heat treatment are the same as those for the film after the sequential biaxial stretching.
[0257] <Size>
[0258] The optical plastic film may be in the form of a single leaf cut into a predetermined size, or in the form of a roll formed by rolling a long sheet. The size of the single leaf is not particularly limited, and the maximum diameter is about 14.2 inches to 500 inches. The "maximum diameter" refers to the maximum length when any two points of the optical plastic film are connected. For example, when the optical plastic film is rectangular, the diagonal of the rectangle is the maximum diameter. When the optical plastic film is circular, the diameter of the circle is the maximum diameter.
[0259] The width and length of the roll are not particularly limited, but generally, the width is between 300 mm and 9000 mm, and the length is between 100 m and 5000 m. The roll-shaped optical plastic film can be cut into a single leaf shape according to the size of the image display device, etc. When cutting, it is preferred that the end of the roll, which has unstable physical properties, is excluded.
[0260] The shape of a single leaf is not particularly limited, and may be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or may be a circle, or may be a random amorphous shape.
[0261] <Purpose>
[0262] The optical plastic film of the present invention can be suitably used as a plastic film for image display devices.
[0263] In addition, as described above, the plastic film of the present invention can suppress the remaining bending marks or breakage after the bending test regardless of the bending direction, so it can be more suitable as a plastic film for foldable image display devices, rollable image display devices, and image display devices with curved shapes.
[0264] The optical plastic film of the present invention can be suitably used as a plastic film disposed on the light emitting surface side of a display element of an image display device. In this case, it is preferred that a polarizing element is provided between the display element and the optical plastic film of the present invention.
[0265] Examples of the plastic film for the image display device include plastic films used as base materials for various functional films such as polarizer protective films, surface protective films, antireflection films, and conductive films constituting touch panels.
[0266] [Optical layered body]
[0267] The optical layered body of the present invention has a functional layer on the optical plastic film of the present invention.
[0268] As the functional layer, one or more selected from a hard coating layer, an anti-reflection layer, an anti-glare layer, a phase difference layer, an adhesive layer, a transparent conductive layer, an antistatic layer, and an antifouling layer can be cited. Among the above-mentioned functional layers, the phase difference layer represented by the liquid crystal layer has a tendency to have weak physical properties such as pencil hardness and insufficient light resistance. Therefore, in the case where the optical layered body has a phase difference layer, in the image display device, it is preferred to configure the phase difference layer side of the optical layered body to face the display element side based on the plastic film.
[0269] The functional layer of the optical layered body preferably includes an antireflection layer. The antireflection layer is preferably disposed on the outermost surface of the plastic film on the side having the functional layer.
[0270] By including an antireflection layer as a functional layer of the optical layered body, rainbow spots can be further suppressed.
[0271] The optical plastic film constituting the optical layered body of the present invention can easily improve the pencil hardness by satisfying the specified preferred conditions as described above. Therefore, the optical layered body of the present invention can also easily improve the pencil hardness. Thus, the optical layered body of the present invention can be suitably used as a surface material for an image display device. It should be noted that, when the optical layered body of the present invention is used as a surface material for an image display device, there is no phase difference layer as a functional layer on the observation side.
[0272] The functional layer more preferably includes a hard coating layer and an anti-reflection layer. In the case where the functional layer includes a hard coating layer and an anti-reflection layer, it is preferred that a hard coating layer 41 and an anti-reflection layer 42 are sequentially arranged on the plastic film 10 ( Figure 3 ). When the functional layer includes a hard coat layer and an antireflection layer, suitability as a surface material for an image display device can be improved.
[0273] Examples of the antireflection layer include a single-layer structure of a low-refractive index layer, a two-layer structure of a high-refractive index layer and a low-refractive index layer, and a multi-layer structure of three or more layers.
[0274] The low refractive index layer is preferably disposed on the outermost surface of the plastic film on the side having the functional layer.
[0275] The lower limit of the refractive index of the low refractive index layer is preferably 1.10 or more, more preferably 1.20 or more, more preferably 1.26 or more, more preferably 1.28 or more, more preferably 1.30 or more, and the upper limit is preferably 1.48 or less, more preferably 1.45 or less, more preferably 1.40 or less, more preferably 1.38 or less, more preferably 1.32 or less.
[0276] Examples of the range of the refractive index of the low refractive index layer include 1.10 to 1.48, 1.10 to 1.45, 1.10 to 1.40, 1.10 to 1.38, 1.10 to 1.32, 1.20 to 1.48, 1.20 to 1.45, 1.20 to 1.40, 1.20 to 1.38, 1.20 to 1.32, 1.26 to 1.48, 1.26 to 1.48, .45 and below, 1.26 to 1.40, 1.26 to 1.38, 1.26 to 1.32, 1.28 to 1.48, 1.28 to 1.45, 1.28 to 1.40, 1.28 to 1.38, 1.28 to 1.32, 1.30 to 1.48, 1.30 to 1.45, 1.30 to 1.40, 1.30 to 1.38, 1.30 to 1.32.
[0277] In this specification, the refractive index of a layer constituting an antireflection layer such as a low refractive index layer and a high refractive index layer refers to a value at a wavelength of 589.3 nm.
[0278] The lower limit of the thickness of the low refractive index layer is preferably 80 nm or more, more preferably 85 nm or more, more preferably 90 nm or more, and the upper limit is preferably 150 nm or less, more preferably 110 nm or less, more preferably 105 nm or less.
[0279] Embodiments of the range of the thickness of the low refractive index layer include 80 nm to 150 nm, 80 nm to 110 nm, 80 nm to 105 nm, 85 nm to 150 nm, 85 nm to 110 nm, 85 nm to 105 nm, 90 nm to 150 nm, 90 nm to 110 nm, and 90 nm to 105 nm.
[0280] The method of forming a low refractive index layer can be roughly divided into a wet method and a dry method. As a wet method, there are: a method of forming by a sol-gel method using a metal alkoxide or the like; a method of forming by coating a low refractive index resin such as a fluororesin; a method of forming by coating a low refractive index layer-forming coating liquid containing low refractive index particles in a resin composition. As a dry method, there are methods of forming a low refractive index layer by a physical vapor growth method or a chemical vapor deposition method. As materials, there are SiO2, SiO x (x=1 or more and 2 or less), MgF2, etc.
[0281] From the perspective of production efficiency, suppression of oblique reflection hue, and chemical resistance, the wet method is superior to the dry method. In the present embodiment, in the wet method, from the perspective of adhesion, water resistance, scratch resistance, and low refractive index, it is preferably formed by a low refractive index layer-forming coating liquid containing low refractive index particles in a binder resin composition. In other words, the low refractive index layer preferably comprises a binder resin and low refractive index particles.
[0282] The binder resin of low refractive index layer preferably comprises the cured product of curable resin composition.Relative to the whole binder resin of low refractive index layer, the ratio of the cured product of curable resin composition is preferably more than 50 mass %, more preferably more than 70 mass %, more preferably more than 90 mass %, most preferably 100 mass %.
[0283] Examples of the curable resin composition of the low refractive index layer include a thermosetting resin composition and an ionizing radiation curable resin composition. As the curable resin composition such as the thermosetting resin composition and the ionizing radiation curable resin composition, a general-purpose composition can be used.
[0284] The low refractive index particles preferably include one or more selected from hollow particles and non-hollow particles. In order to balance low reflection and scratch resistance, it is preferred to use one or more selected from hollow particles and one or more selected from non-hollow particles in combination.
[0285] The material of the hollow particles and the non-hollow particles can be any of inorganic compounds such as silicon dioxide and magnesium fluoride, and organic compounds. For the reasons of low refractive index and strength, silicon dioxide is preferred. That is, the low refractive index layer preferably includes hollow silica particles and non-hollow silica particles as low refractive index particles.
[0286] If taking into account optical properties and mechanical strength, the lower limit of the average particle size of the hollow particles is preferably more than 50nm, more preferably more than 60nm, and the upper limit is preferably less than 100nm, more preferably less than 80nm. As an embodiment of the range of the average particle size of the hollow particles, 50nm to 100nm, 50nm to 80nm, 60nm to 100nm, 60nm to 80nm, can be cited.
[0287] If the agglomeration of the non-hollow particles is prevented and the dispersibility is taken into consideration, the lower limit of the average particle size of the non-hollow particles is preferably 5 nm or more, more preferably 10 nm or more, and the upper limit is preferably 20 nm or less, more preferably 15 nm or less. As embodiments of the range of the average particle size of the non-hollow particles, 5 nm or more and 20 nm or less, 5 nm or more and 15 nm or less, 10 nm or more and 20 nm or less, 10 nm or more and 15 nm or less can be cited.
[0288] The more the content of hollow particles, the higher the filling rate of the hollow particles in the binder resin, and the lower the refractive index of the low refractive index layer. Therefore, the content of hollow particles is preferably 100 parts by mass or more, more preferably 150 parts by mass or more relative to 100 parts by mass of the binder resin.
[0289] On the other hand, if the content of hollow particles is too much relative to the binder resin, the hollow particles exposed from the binder resin increase, and the binder resin between the bonding particles decreases, thus having a tendency that the mechanical strength such as the scratch resistance of the low refractive index layer decreases. Therefore, the content of hollow particles is preferably less than 400 mass parts, more preferably less than 300 mass parts relative to 100 mass parts of the binder resin.
[0290] Examples of the range of the content of the hollow particles per 100 parts by mass of the binder resin include 100 to 400 parts by mass, 100 to 300 parts by mass, 150 to 400 parts by mass, and 150 to 300 parts by mass.
[0291] When the content of non-hollow particles is few, even if there is non-hollow particles on the surface of low-refractive index layer, sometimes hardness rising will not be affected.On the other hand, when the content of non-hollow particles is many, the impact of the shrinkage unevenness caused by the polymerization of binder resin tapers, so that the concavo-convexity produced on the surface of low-refractive index layer after resin curing tapers, so it is easier to improve scratch resistance.Therefore, the content of non-hollow particles is preferably more than 10 mass parts, more preferably more than 50 mass parts, more preferably more than 70 mass parts, more preferably more than 100 mass parts relative to 100 mass parts of binder resin.
[0292] On the other hand, when the content of non-hollow particles is too much, the shrinkage of the binder resin is uneven due to the easy aggregation of non-hollow particles, so the surface concavoconvex becomes larger. Therefore, the content of non-hollow particles is preferably less than 200 mass parts, more preferably less than 150 mass parts relative to 100 mass parts of binder resin.
[0293] As embodiments of the range of the content of non-hollow particles relative to 100 parts by mass of the binder resin, there can be cited 10 parts by mass to 200 parts by mass, 10 parts by mass to 150 parts by mass, 50 parts by mass to 200 parts by mass, 50 parts by mass to 150 parts by mass, 70 parts by mass to 200 parts by mass, 70 parts by mass to 150 parts by mass, 100 parts by mass to 200 parts by mass, and 100 parts by mass to 150 parts by mass.
[0294] The high refractive index layer is preferably disposed on the plastic film side of the low refractive index layer. In the case of having a hard coat layer described below, the high refractive index layer is preferably formed between the hard coat layer and the low refractive index layer.
[0295] The lower limit of the refractive index of the high refractive index layer is preferably 1.53 or more, more preferably 1.54 or more, more preferably 1.55 or more, more preferably 1.56 or more, and the upper limit is preferably 1.85 or less, more preferably 1.80 or less, more preferably 1.75 or less, more preferably 1.70 or less.
[0296] Embodiments of the range of the refractive index of the high refractive index layer include 1.53 to 1.85, 1.53 to 1.80, 1.53 to 1.75, 1.53 to 1.70, 1.54 to 1.85, 1.54 to 1.80, 1.54 to 1.75, 1.54 to 1.70, 1.55 to 1.85, 1.55 to 1.80, 1.55 to 1.75, 1.55 to 1.70, 1.56 to 1.85, 1.56 to 1.80, 1.56 to 1.75, 1.56 to 1.70.
[0297] The upper limit of the thickness of the high refractive index layer is preferably 200 nm or less, more preferably 180 nm or less, and further preferably 150 nm or less, and the lower limit is preferably 50 nm or more, and more preferably 70 nm or more.
[0298] Examples of the thickness range of the high refractive index layer include 200 nm or less, 50 nm to 200 nm or less, 50 nm to 180 nm or less, 50 nm to 150 nm or less, 70 nm to 200 nm or less, 70 nm to 180 nm or less, and 70 nm to 150 nm or less.
[0299] When forming a high refractive index hard coat layer, it is preferable to use the thickness of the hard coat layer as a reference.
[0300] The high refractive index layer can be formed, for example, from a high refractive index layer-forming coating liquid containing a binder resin composition and high refractive index particles. That is, the high refractive index layer preferably contains a binder resin and high refractive index particles.
[0301] The binder resin of the high refractive index layer preferably comprises a cured product of a curable resin composition. Relative to the whole binder resin of the high refractive index layer, the ratio of the cured product of the curable resin composition is preferably 50% by mass or more, more preferably 70% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass.
[0302] Examples of the curable resin composition of the high refractive index layer include a thermosetting resin composition and an ionizing radiation curable resin composition. As the curable resin composition such as the thermosetting resin composition and the ionizing radiation curable resin composition, a general-purpose composition can be used.
[0303] Examples of high refractive index particles include antimony pentoxide (refractive index: about 1.79), zinc oxide (refractive index: about 1.90), titanium oxide (refractive index: about 2.3 to 2.7), cerium oxide (refractive index: about 1.95), tin-doped indium oxide (refractive index: about 1.95 to 2.00), antimony-doped tin oxide (refractive index: about 1.75 to 1.85), yttrium oxide (refractive index: about 1.87) and zirconium oxide (refractive index: about 2.10).
[0304] The average particle size of the high refractive index particles is preferably 2 nm or more, more preferably 5 nm or more, and further preferably 10 nm or more. In addition, for the purpose of suppressing whitening and transparency, the average particle size of the high refractive index particles is preferably 200 nm or less, more preferably 100 nm or less, more preferably 80 nm or less, more preferably 60 nm or less, and more preferably 30 nm or less.
[0305] As embodiments of the range of the average particle size of the high refractive index particles, there can be cited 2 nm to 200 nm, 2 nm to 100 nm, 2 nm to 80 nm, 2 nm to 60 nm, 2 nm to 30 nm, 5 nm to 200 nm, 5 nm to 100 nm, 5 nm to 80 nm, 5 nm to 60 nm, 5 nm to 30 nm, 10 nm to 200 nm, 10 nm to 100 nm, 10 nm to 80 nm, 10 nm to 60 nm, and 10 nm to 30 nm.
[0306] The average particle size of the high refractive index particles or the low refractive index particles can be calculated by the following operations (y1) to (y3).
[0307] (y1) STEM is used to photograph a cross section of a high refractive index layer or a low refractive index layer. The acceleration voltage of STEM is preferably 10 kV to 30 kV, and the magnification is preferably 50,000 to 300,000 times. As a commercially available STEM, a field emission scanning electron microscope "Part No.: S-4800" of Hitachi High-Technologies Corporation can be cited.
[0308] (y2) After extracting any 10 particles from the observed image, calculate the particle size of each particle. The particle size is measured as the distance between two straight lines in a combination of two straight lines that have the largest distance between the two straight lines when the cross section of the particle is sandwiched between any two parallel straight lines. In the case of particle aggregation, the aggregated particles are measured as one particle.
[0309] (y3) The same operation is performed five times on another observation image of the same sample, and the value obtained from the number average of 50 particle diameters is taken as the average particle diameter of the high refractive index particles or the low refractive index particles.
[0310] The hard coat layer preferably contains a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition as a main component. As the curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition, a general-purpose composition can be used.
[0311] The main component means that it accounts for 50% by mass or more, preferably 70% by mass or more, and more preferably 90% by mass or more of the resin component constituting the hard coat layer.
[0312] The lower limit of the thickness of the hard coat layer is preferably 0.5 μm or more, more preferably 1 μm or more, and the upper limit is preferably 30 μm or less, more preferably 10 μm or less.
[0313] Examples of the range of the thickness of the hard coat layer include 0.5 μm to 30 μm, 0.5 μm to 10 μm, 1 μm to 30 μm, and 1 μm to 10 μm.
[0314] <Size>
[0315] The optical layered body can be in the form of a single leaf cut into a specified size, or in the form of a roll in which a long sheet is rolled up. The size of the single leaf is not particularly limited, and the maximum diameter is about 14.2 inches or more and 500 inches or less. "Maximum diameter" refers to the maximum length when connecting any two points of the optical layered body. For example, when the optical layered body is a rectangle, the diagonal of the rectangle is the maximum diameter. When the optical layered body is a circle, the diameter of the circle is the maximum diameter.
[0316] The width and length of the roll are not particularly limited, and generally, the width is between 300 mm and 9000 mm, and the length is between 100 m and 5000 m. The roll-shaped optical layered body can be cut into a single leaf shape for use according to the size of the image display device, etc. When cutting, it is preferred that the roll end portion, which has unstable physical properties, is excluded.
[0317] The shape of a single leaf is not particularly limited, and may be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or may be a circle, or may be a random amorphous shape.
[0318] [Polarizing plate]
[0319] The polarizing plate of the present invention is a polarizing plate comprising a polarizing element, a first transparent protective plate arranged on one side of the polarizing element, and a second transparent protective plate arranged on the other side of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate comprises the optical plastic film of the present invention.
[0320] The polarizing plate is used to impart antireflection properties by combining the polarizing plate with a λ / 4 phase difference plate, for example. In this case, the λ / 4 phase difference plate is disposed on the display element of the image display device, and the polarizing plate is disposed on the observer side relative to the λ / 4 phase difference plate.
[0321] When the polarizer is used in a liquid crystal display device, the polarizer is used to give the liquid crystal light valve function. In this case, the liquid crystal display device is arranged in the order of a lower polarizer, a liquid crystal display element, and an upper polarizer, and the absorption axis of the polarizer of the lower polarizer is arranged orthogonal to the absorption axis of the polarizer of the upper polarizer. In the above configuration, it is preferred to use the polarizer of the present invention as the upper polarizer.
[0322] <Transparent protective plate>
[0323] The polarizing plate of the present invention comprises the optical plastic film of the present invention as at least one of the first transparent protective plate and the second transparent protective plate. In a preferred embodiment, both the first transparent protective plate and the second transparent protective plate comprise the optical plastic film of the present invention.
[0324] When one of the first transparent protective plate and the second transparent protective plate includes the optical plastic film of the present invention, the other transparent protective plate is not particularly limited, but is preferably an optically isotropic transparent protective plate.
[0325] In this specification, optical isotropy means that the in-plane retardation is 20 nm or less, preferably 10 nm or less, and more preferably 5 nm or less. Acrylic films and triacetylcellulose (TAC) films can be easily provided with optical isotropy.
[0326] When one of the first transparent protective plate and the second transparent protective plate includes the optical plastic film of the present invention, the transparent protective plate on the light emitting side preferably includes the optical plastic film of the present invention.
[0327] The polarizing plate of the present invention also preferably uses the optical layered body of the present invention as at least one of the first transparent protective plate and the second transparent protective plate.
[0328] <Polarizing Element>
[0329] As polarizing elements, there can be mentioned sheet-type polarizing elements such as polyvinyl alcohol film, polyvinyl formal film, polyvinyl acetal film, ethylene-vinyl acetate copolymer saponified film, etc., which are dyed with iodine or the like and stretched; wire grid polarizing elements composed of a large number of metal wires arranged in parallel; coating polarizing elements coated with lyotropic liquid crystal or dichroic host-guest material; multilayer thin film polarizing elements, etc. These polarizing elements can be reflective polarizing elements having the function of reflecting non-transmitted polarized components.
[0330] The average angle between the direction of the absorption axis of the polarizing element and the direction of the slow axis of the optical plastic film is not particularly limited, and is preferably configured to be approximately parallel or approximately perpendicular. In this specification, approximately parallel means within 0 degrees ± 5 degrees, preferably within 0 degrees ± 3 degrees, and more preferably within 0 degrees ± 1 degree. In this specification, approximately perpendicular means within 90 degrees ± 5 degrees, preferably within 90 degrees ± 3 degrees, and more preferably within 90 degrees ± 1 degree. Generally, it is difficult to suppress a black screen when the angle between the absorption axis of the polarizing element and the direction of the slow axis of the optical plastic film is approximately parallel or approximately perpendicular. However, since the polarizing plate of the present invention uses the optical plastic film of the present invention, a black screen can be suppressed even if the above angles are approximately parallel or approximately perpendicular. In addition, by making the above angles approximately parallel or approximately perpendicular, the yield of the polarizing element and the optical plastic film can be easily improved.
[0331] <Size>
[0332] The polarizer may be in the form of a single leaf cut into a specified size, or in the form of a roll in which a long sheet is rolled up. The size of the single leaf is not particularly limited, and the maximum diameter is about 14.2 inches to 500 inches. The "maximum diameter" refers to the maximum length when any two points of the polarizer are connected. For example, when the polarizer is rectangular, the diagonal of the rectangle is the maximum diameter. When the polarizer is circular, the diameter of the circle is the maximum diameter.
[0333] The width and length of the roll are not particularly limited, and generally, the width is between 300 mm and 9000 mm, and the length is between 100 m and 5000 m. The roll-shaped polarizing plate can be cut into a single leaf shape for use according to the size of the image display device, etc. When cutting, it is preferred that the end of the roll with unstable physical properties is excluded.
[0334] The shape of a single leaf is not particularly limited, and may be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or may be a circle, or may be a random amorphous shape.
[0335] [Image display device]
[0336] The image display device of the present invention is an image display device comprising a display element and a plastic film disposed on the light emitting surface side of the display element, wherein the plastic film is the optical plastic film of the present invention.
[0337] Figure 3 and Figure 4 It is a cross-sectional view showing an embodiment of an image display device 100 of the present invention.
[0338] Figure 3 and Figure 4 The image display device 100 includes an optical plastic film 10 on the light emitting surface side of a display element 20 . Figure 3 and Figure 4 The upper side is the light emitting surface side of the display element. Figure 3 and Figure 4 Each of the image display devices 100 includes a polarizing element 31 between the display element 20 and the optical plastic film 10 . Figure 3 and Figure 4 In the embodiment, a first transparent protective plate (32) and a second transparent protective plate (33) are stacked on both surfaces of a polarizing element 31. Figure 4 In the image display device, an optical plastic film 10 is used as a first transparent protective plate (32).
[0339] When a polarizing element is provided between the display element and the optical plastic film, the average angle between the absorption axis of the polarizing element and the slow axis of the optical plastic film is not particularly limited, but is preferably arranged substantially parallel or substantially perpendicularly.
[0340] The image display device 100 is not limited to Figure 3 and Figure 4 For example, in Figure 3 and Figure 4 In the figure, the components constituting the image display device 100 are arranged at predetermined intervals, but the components may be integrated via an adhesive layer, etc. The image display device may also include components not shown.
[0341] <Display Components>
[0342] Examples of display elements include liquid crystal display elements, EL display elements such as organic EL display elements and inorganic EL display elements, plasma display elements, and further include LED display elements such as Micro LED display elements and micro LED display elements.
[0343] When the display element of the display device is a liquid crystal display element, a backlight is required on the surface of the liquid crystal display element on the opposite side to the resin sheet.
[0344] The display element preferably has a wide color gamut. As described later, the spectral spectra of RGB of a display element having a wide color gamut are sharp. Furthermore, if the shape of the spectral spectrum of the display element is sharp, it is difficult to suppress rainbow spots by increasing the in-plane phase difference. Since the in-plane phase difference of the optical plastic film of the present invention is small, it is easy to suppress rainbow spots even when the color gamut of the display element is wide, and it is preferred from this point of view.
[0345] The color gamut that can be reproduced by mixing the three colors of RGB is represented by a triangle on the CIE-xy chromaticity diagram. The triangle is formed by determining the vertex coordinates of each RGB color and connecting the vertices.
[0346] When the spectral spectra of RGB are sharp, the value of x of the vertex coordinate of R is large and the value of y is small, the value of x of the vertex coordinate of G is small and the value of y is large, and the value of x of the vertex coordinate of B is small and the value of y is small. That is, when the spectral spectra of RGB are sharp, the area of the triangle formed by connecting the vertex coordinates of each color of RGB in the CIE-xy chromaticity diagram becomes larger, and the width of the color gamut that can be reproduced becomes wider. In addition, the width of the color gamut becomes wider, which will lead to the improvement of the appeal and sense of presence of dynamic images.
[0347] As a standard for expressing color gamut, "ITU-R Recommendation BT.2020-2 (hereinafter referred to as "BT.2020-2")" is cited. ITU-R is the abbreviation of "International Telecommunication Union-Radiocommunication Sector", and ITU-R Recommendation BT.2020-2 is an international standard for ultra-high-definition color gamut revised in October 2015. When the coverage of BT.2020-2 based on the CIE-xy chromaticity diagram represented by the following formula is in the range described below, the appeal and sense of presence of dynamic images can be easily improved.
[0348] <Formula representing the coverage of BT.2020-2>
[0349] [Area of the CIE-xy chromaticity diagram of light emitted from the display element that overlaps with the area of the CIE-xy chromaticity diagram of BT.2020-2 / Area of the CIE-xy chromaticity diagram of BT.2020-2] × 100 (%)
[0350] Regarding the "area of the CIE-xy chromaticity diagram of light emitted from the display element" required for calculating the coverage of BT.2020-2, the x value and y value of the CIE-Yxy chromaticity system when red display, green display, and blue display are measured respectively, and can be calculated by the "vertex coordinates of red", "vertex coordinates of green", and "vertex coordinates of blue" obtained from the above measurement results. The x value and y value of the CIE-Yxy chromaticity system can be measured, for example, using a spectral radiance meter CS-2000 manufactured by Konica Minolta.
[0351] The display element preferably has a coverage of BT.2020-2 calculated by the above formula of 60% or more, more preferably 65% or more. Since the in-plane phase difference of the optical plastic film of the present invention is small, even if the coverage of BT.2020-2 of the display element is 60% or more, rainbow spots can be easily suppressed, which is preferred from this point of view.
[0352] The image display device may be an image display device having a touch panel function.
[0353] Examples of the touch panel include a resistive film type, an electrostatic capacitance type, an electromagnetic induction type, an infrared type, and an ultrasonic type.
[0354] The touch panel function may be added to the display element as in a built-in touch panel liquid crystal display element, or a touch panel may be mounted on the display element.
[0355] As described above, the optical plastic film of the present invention can suppress the bending marks from remaining or the occurrence of fractures after the bending test. Therefore, the image display device of the present invention can exert a more significant effect in the case of a foldable image display device (foldable image display device), a rollable image display device (rollable image display device that can be deformed from a curved surface shape to a flat shape), or an image display device with a curved surface shape, which is preferred from this point of view.
[0356] When the image display device is a foldable image display device, a rollable image display device, or an image display device having a curved shape, the display element is preferably an organic EL display element.
[0357] <Plastic film>
[0358] The image display device of the present invention has the optical plastic film of the present invention on the light emitting surface side of the display element. In the image display device, the optical plastic film of the present invention may be only one sheet or may be two or more sheets.
[0359] Examples of the optical plastic film disposed on the light emitting surface side of the display element include optical plastic films used as substrates for various functional films such as polarizer protective films, surface protective films, antireflection films, and conductive films constituting touch panels.
[0360] <Other plastic films>
[0361] The image display device of the present invention may include other plastic films within a range that does not impair the effects of the present invention. Other plastic films are plastic films that do not satisfy the conditions of the optical plastic film of the present invention.
[0362] As other plastic films, it is preferable that the films have optical isotropy. In the present specification, optical isotropy means that the in-plane retardation is 20 nm or less.
[0363] <Size>
[0364] The size of the image display device is not particularly limited, and the maximum diameter is about 14.2 inches to 500 inches. The "maximum diameter" refers to the maximum length when connecting any two points of the image display device. For example, when the image display device is rectangular, the diagonal of the rectangle is the maximum diameter. When the image display device is circular, the diameter of the circle is the maximum diameter.
[0365] The shape of the image display device is not particularly limited, and may be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or may be a circle, or may be a random amorphous shape.
[0366] Example
[0367] Next, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0368] 1. Measurement and evaluation
[0369] The following measurements and evaluations were performed at a temperature of 23°C ± 5°C and a relative humidity of 40% to 65%. Before the measurements and evaluations, the samples were exposed to the above atmosphere for 30 minutes or more. Each sample was taken from a location without defects in the optical plastic film or functional layer.
[0370] 1-1. In-plane phase difference (Re) and direction of slow axis
[0371] Seven large samples of 200 mm in the flow direction and 300 mm in the width direction were cut from the roll-shaped optical plastic films of Examples 1 to 10 and Comparative Example 6 with a width of 2100 mm produced in "2" described later. The large sample in the center of the width direction was taken as Sample 1 of each Example, the first large sample on the right side compared to the center of the width direction was taken as Sample 2 of each Example, the second large sample on the right side compared to the center of the width direction was taken as Sample 3 of each Example, and the large sample on the right end of the third large sample on the right side compared to the center of the width direction was taken as Sample 4 of each Example. The optical plastic film has roughly equal physical properties at left-right symmetrical positions based on the center of the width direction, so the measurement on the left side of the center of the width direction was omitted. Among them, only samples 2 to 3 were collected for Example 4, only samples 1 to 3 were collected for Example 5, only sample 1 was collected for Examples 7 to 9, only samples 1 were collected for Example 10, and only samples 1 to 2 were collected for Comparative Example 6.
[0372] Thirty small samples of 40 mm×50 mm were cut out from each of the four large samples, Samples 1 to 4, to obtain samples for measurement.
[0373] On the other hand, one large sample of 200 mm×300 mm was cut out from the optical plastic films of Comparative Examples 1 to 5 prepared in “2” described later, and 30 small samples of 40 mm×50 mm were cut out from the large sample to obtain samples for measurement.
[0374] Next, the in-plane phase difference and the angle of the slow axis were measured in an area of 30 mm × 40 mm after removing 5 mm from the edge of the 40 mm × 50 mm measurement sample of the embodiment and the comparative example. The measurement device used was the trade name "WPA-200-L" of Photonic Lattice. The measurement conditions and the like are as follows. Through this measurement, the in-plane phase difference and the angle of the slow axis of each area after the 30 mm × 40 mm area is subdivided into more than 47,000 areas can be measured.
[0375] Based on the measurement results, for the 30 small samples that make up a large sample, the average value of the in-plane phase difference and the standard deviation σ of the angle of the slow axis were calculated respectively, and then it was determined whether each large sample satisfied Conditions 1 to 2. When the conditions were satisfied, it was marked as "A", and when not satisfied, it was marked as "C". The results are shown in Table 1 or 2.
[0376] In addition, based on the average value of the in-plane phase difference, the standard deviation σ of the in-plane phase difference, and the standard deviation σ of the angle of the slow axis calculated from each small sample, the average value of the 30 small samples was calculated. The results are shown in Table 3.
[0377] It should be noted that the in-plane phase difference above 3000 nm cannot be measured with the product name "WPA-200-L" of Photonic Lattice. Therefore, only the standard deviation σ of the angle of the slow axis of the measurement sample in Comparative Example 5 was measured using the product name "WPA-200-L" of Photonic Lattice. In addition, the in-plane phase difference of the measurement sample in Comparative Example 5 was measured for the in-plane center value of the sample using the product name "RETS-100" manufactured by Otsuka Electronics Co., Ltd.
[0378] <Specifications of WPA-200-L>
[0379] · Number of birefringent pixels: 384 × 288 pixels
[0380] · Lens: Standard lens (f1.25)
[0381] <Measurement steps>
[0382] (1) Turn on the power of the device and start the software (WPA-view), and then wait at least 30 minutes to make it stable.
[0383] (2) After placing the measurement sample on the light source stage, while adjusting the height of the camera unit, place the measurement sample within the area reflected by the light source stage in the camera preview window. At this time, ensure that the measurement sample does not float from the light source stage. In addition, visually confirm that no external light is reflected in the preview window. The area reflected by the light source stage in the camera preview window is divided into 384 × 288 pixels (110,592 pixels). It should be noted that in the camera preview window, it is preferable to make the above adjustments so that there is a certain gap between the outer edge of the measurement sample and the outer edge of the area reflected by the light source stage. The above gap is preferably about 3 mm in actual size.
[0384] (3) While turning the dial of the lens, focus on the measurement sample. In the measurement of the embodiment, the scale of the dial was set to "4".
[0385] (4) In the user settings, set the following conditions. Next, temporarily remove the sample for measurement and measure the baseline. Perform the baseline measurement for each sample.
[0386] (5) The sample is arranged again and then the measurement is performed.
[0387] (6) On the analysis screen, an area of the sample corresponding to an actual area of 30 mm×40 mm is selected, and the average value of the in-plane phase difference, the standard deviation σ of the in-plane phase difference, and the standard deviation σ of the slow axis angle are calculated.
[0388] <User Settings>
[0389] In User Settings, check the following items.
[0390] Automatic exposure adjustment: Automatic exposure adjustment during measurement
[0391] Noise filter: Automatically applied
[0392] · Masking of dark areas: Masking (10.0%)
[0393] ·Axis direction setting: Slow axis
[0394] ·Measurement accuracy: high accuracy
[0395] ·Measurement mode: 3 wavelength measurement
[0396] Material coefficient: Automatic
[0397] 1-2. Retardation in the thickness direction (Rth)
[0398] The retardation in the thickness direction of the center of a 30 mm × 40 mm region after removing 5 mm from the edge of the 30 40 mm × 50 mm measurement samples of Examples and Comparative Examples prepared in 1-1 was measured. The measurement device used was a product name "RETS-100" manufactured by Otsuka Electronics Co., Ltd.
[0399] Based on the measurement results, it was determined whether the large sample satisfied condition 3. If the condition was satisfied, it was recorded as "A", and if it was not satisfied, it was recorded as "C". The results are shown in Table 1 or 2.
[0400] In addition, based on the phase difference in the thickness direction calculated from each small sample, the average value of 30 small samples was calculated.
[0401] 1-3. Erosion rate
[0402] The erosion rate of the plastic film constituting the sample from the surface to a depth of 20 μm was measured at the center of a 30 mm × 40 mm area after removing 5 mm from the edge of the 30 40 mm × 50 mm measurement samples of the examples and comparative examples prepared in 1-1. Then, the average value E of the erosion rate of the plastic film constituting the sample from the surface to a depth of 20 μm was calculated from the obtained erosion rate. 0-20 The method for measuring the erosion rate is in accordance with the description in the main text of the specification.
[0403] Based on the measurement results, it was determined whether the large sample satisfied condition 5. If the condition was satisfied, it was recorded as "A", and if it was not satisfied, it was recorded as "C". The results are shown in Table 1 or 2.
[0404] 1-4. Rainbow spot 1 (liquid crystal display device with plastic film alone and white LED as light source)
[0405] A large sample of 200 mm × 300 mm of the embodiment and comparative example prepared in 1-1 is arranged on the observation side polarizing plate of the image display device 1 of the following structure. The absorption axis of the polarizing element of the observation side polarizing plate is arranged to be parallel to the average direction of the slow axis of the large sample. Next, the image display device is lit in a dark room environment, and the sample is observed with the naked eye from various angles along the slow axis of the measurement sample from a distance of about 1 m, and the presence or absence of rainbow spots is evaluated based on the following criteria. The evaluators are 20 healthy people of each generation, 5 from 20 to 59 years old, with a corrected visual acuity of 1.0 or above.
[0406] A: More than 16 people answered that they could not observe rainbow spots.
[0407] B: More than 11 and less than 15 people answered that they could not observe rainbow spots.
[0408] C: Less than 10 people answered that they could not observe rainbow spots.
[0409] <Configuration of Image Display Device 1>
[0410] (1) Backlight: White LED
[0411] (2) Display element: Liquid crystal display element with color filter
[0412] (3) Light source side polarizing plate: TAC films were provided as protective films on both sides of a polarizing element made of PVA and iodine, and the polarizing element was arranged so that the absorption axis of the polarizing element was perpendicular to the horizontal direction of the screen.
[0413] (4) Image display unit: Liquid crystal unit
[0414] (5) Observation-side polarizing plate: A polarizing plate using a TAC film as a polarizing element protective film of a polarizing element composed of PVA and iodine. The polarizing element was arranged so that the absorption axis direction of the polarizing element was parallel to the horizontal direction of the screen.
[0415] (6) Size: 21.5 inches diagonally
[0416] The coverage of BT.2020-2 based on the CIE-xy chromaticity diagram of the image display device 1 is 49%.
[0417] 1-5. Rainbow spot 2 (Plastic film alone, organic EL display device)
[0418] The rainbow spots were evaluated in the same manner as in 1-4 except that the image display device 1 was changed to the image display device 2 described below.
[0419] <Configuration of Image Display Device 2>
[0420] (1) Display element: Organic EL display element with three independent colors and microcavity structure
[0421] (2) Polarizer on light source side: None
[0422] (3) Observation-side polarizing plate: A polarizing plate using a TAC film as a polarizing element protective film of a polarizing element composed of PVA and iodine. The polarizing element was arranged so that the absorption axis direction of the polarizing element was parallel to the horizontal direction of the screen.
[0423] (4) Size: 21.5 inches diagonally
[0424] The coverage of BT.2020-2 based on the CIE-xy chromaticity diagram of the image display device 2 is 77%.
[0425] 1-6. Rainbow Spot 3 (Optical Layered Body, Liquid Crystal Display Device with White LED as Light Source)
[0426] The rainbow spots were evaluated in the same manner as in 1-4 except that the plastic films of Examples and Comparative Examples disposed on the polarizing plate on the observation side were changed to the optical layered bodies of Examples and Comparative Examples prepared in the following "3".
[0427] 1-7. Rainbow spots 4 (optical layered body, organic EL display device)
[0428] The rainbow spots were evaluated in the same manner as in 1-5 except that the plastic films of Examples and Comparative Examples disposed on the polarizing plate on the observation side were changed to the optical layered bodies of Examples and Comparative Examples prepared in the following "3".
[0429] 1-8. Black screen 1 (vertical configuration)
[0430] The large samples of 200 mm × 300 mm of the embodiment and comparative example prepared in 1-1 are arranged on the observation side polarizing plate of the image display device 1 of the structure shown in 1-4. Each sample is arranged so that the average direction of the slow axis of the sample is perpendicular to the horizontal direction of the screen. In other words, the angle formed by the absorption axis of the polarizing element of the observation side polarizing plate and the average direction of the slow axis of the sample is 90 degrees.
[0431] Next, in the central part of the image display device equipped with the sample, three characters with a font size of 16 were displayed at a display magnification of 100% using the trade name "WORD (registered trademark)" of Microsoft Corporation, and then observed from the front through polarized sunglasses. The direction of the absorption axis of the polarized sunglasses during observation is the direction orthogonal to the absorption axis of the polarizing element of the polarizer on the observation side. 3 points were given when the characters could be easily distinguished, 1 point was given when the characters could not be easily distinguished due to a black screen, and 2 points were given when neither of the two was true. The evaluation was conducted by 5 subjects from each generation aged 20 to 59, for a total of 20 subjects. The average score of the 20 people's evaluation was calculated and ranked according to the following criteria. The 20 subjects were all healthy people with a visual acuity of 1.0 or above. The above visual acuity includes corrected visual acuity.
[0432] <Evaluation Criteria>
[0433] AAA: Average score is 2.85 or above
[0434] AA: Average score is 2.70 or higher and less than 2.85
[0435] A: The average score is 2.50 or more and less than 2.70
[0436] B: Average score is 2.00 or more and less than 2.50
[0437] C: The average score is 1.50 or more and less than 2.00
[0438] D: Average score less than 1.50
[0439] 1-9. Black screen 2 (45 degree configuration)
[0440] The large samples of 200 mm × 300 mm of the embodiment and comparative example prepared in 1-1 are arranged on the observation side polarizing plate of the image display device 1 of the structure shown in 1-4. Each sample is arranged so that the average direction of the slow axis of the sample is 45 degrees to the horizontal direction of the screen. In other words, the angle formed by the absorption axis of the polarizing element of the observation side polarizing plate and the average direction of the slow axis of the sample is 45 degrees.
[0441] Next, three characters with a font size of 16 were displayed at a display magnification of 100% using the trade name "WORD (registered trademark)" of Microsoft Corporation in the center of the image display device on which the sample was placed, and then observed from the front through polarized sunglasses, and evaluated using the same method as 1 to 8. The direction of the absorption axis of the polarized sunglasses during observation was a direction orthogonal to the absorption axis of the polarizing element of the polarizing plate on the observation side.
[0442] 1-10.Bending resistance
[0443] <Slow axis direction>
[0444] A long strip sample of 30 mm in width direction and 100 mm in flow direction was cut from the central portion in the width direction of the large sample of 200 mm × 300 mm prepared in 1-1 for Examples 1 to 10 and Comparative Example 6. The width direction of the central portion of the optical plastic film of Examples 1 to 10 and Comparative Example 6 roughly represents the average direction of the slow axis.
[0445] Separately, strip samples of 30 mm in the slow axis direction×100 mm in the fast axis direction were cut out from the optical plastic films of Comparative Examples 1 to 5 prepared in “2” described later.
[0446] After fixing the two ends of the short side of the sample to a durability tester (product name "DLDMLH-FS", manufactured by YUASA SYSTEM Co., Ltd.), a continuous folding test of 100,000 folds of 180 degrees was performed. The two ends of the short side of the sample were fixed in an area 10 mm away from the front end of the sample. The folding speed was 120 times per minute. A more detailed method of the folding test is shown below.
[0447] After the folding test, the long strip sample was placed on a horizontal platform, and the angle at which the end of the sample floated from the platform was measured to evaluate the bending resistance in the slow axis direction. The results are shown in Table 1 or 2. If the sample broke in the middle, it was recorded as "broken".
[0448] <Fast axis direction>
[0449] A long strip sample of 30 mm in the flow direction and 100 mm in the width direction was cut from the center of the width direction of the large sample of 200 mm × 300 mm prepared in 1-1 for Examples 1 to 10 and Comparative Example 6. In the center of the optical plastic film of Examples 1 to 10 and Comparative Example 6, the flow direction substantially represents the average direction of the fast axis.
[0450] Separately, strip-shaped samples of 30 mm in the fast axis direction×100 mm in the slow axis direction were cut out from the optical plastic films of Comparative Examples 1 to 5 prepared in “2” described later.
[0451] These samples were subjected to the same measurement as above to evaluate the bending resistance in the fast axis direction.
[0452] <Details of folding test>
[0453] like Figure 5 As shown in (A), in the continuous folding test, first, the side 10C and the side 10D facing the side 10C of the plastic film 10 are fixed by the parallelly arranged fixing parts 60. The fixing parts 60 can slide in the horizontal direction.
[0454] Then, if Figure 5 As shown in (B), the fixing parts 60 are moved so as to approach each other, thereby folding and deforming the plastic film 10. Figure 5 As shown in (C), the fixing part 60 is moved to a position where the interval between two opposing sides of the plastic film 10 fixed by the fixing part 60 is 10 mm, and then the fixing part 60 is moved in the reverse direction, thereby eliminating the deformation of the plastic film 10.
[0455] Through Figure 5 By moving the fixing part 60 as shown in (A) to (C), the plastic film 10 can be folded 180 degrees. In addition, the continuous folding test is performed in such a way that the curved part 10E of the plastic film 10 does not protrude from the lower end of the fixing part 60, and the interval between the fixing parts 60 when they are closest is controlled to 10 mm, thereby making it possible to make the interval between the two sides of the optical film 10 facing each other 10 mm.
[0456] 1-11. Pencil hardness
[0457] As samples for the pencil hardness test, 30 samples of 40 mm × 50 mm for measurement of the examples and comparative examples prepared in 1-1 were prepared. The samples were heated at 100°C for 10 minutes. The pencil hardness test was performed on the heated samples. The pencil hardness test was performed on a 30 mm × 40 mm area after removing 5 mm from the edge of the sample.
[0458] The pencil hardness test was conducted based on the pencil hardness test specified in JIS K5600-5-4:1999, with the load, speed, and judgment conditions modified according to the JIS regulations. Specifically, the load was 100 g and the speed was 3 mm / s. After the load was applied to the heated sample, the sample was heated again at 100°C for 10 minutes before visually evaluating the damage. Then, the damage of the heated sample was visually evaluated.
[0459] The condition for passing the test is that there is no damage at least 3 times out of 5 evaluations. For example, the following judgment method is used: if there is no damage at least 3 times out of 5 times at hardness 2B, hardness 2B is passed, and then the test at hard hardness is performed.
[0460] Table 1 or 2 shows the pencil hardness of the samples of Examples and Comparative Examples, and shows the number of evaluations in which no damage was observed in 5 evaluations. When the pencil hardness results of the 30 samples were different, the pencil hardness of the worst evaluation result is shown in Table 1 or 2.
[0461] The acceptable level was defined as no damage in 3 or more of 5 evaluations at the pencil hardness F. The acceptable level was defined as "AAA" when no damage was found in 5 of 5 evaluations at the pencil hardness F, "AA" when no damage was found in 4 of 5 evaluations at the pencil hardness F, and "A" when no damage was found in 3 of 5 evaluations at the pencil hardness F. The acceptable level was defined as "C".
[0462] 2. Production and preparation of plastic films for optical use
[0463] [Example 1]
[0464] 1 kg of PET (melting point 258°C, absorption center wavelength: 320 nm) and 0.1 kg of ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinone-4-one) were melt-mixed at 280°C using a kneader to prepare pellets containing the ultraviolet absorber. The pellets and PET having a melting point of 258°C were put into a single screw extruder, melt-mixed at 280°C, and extruded from a T die, thereby casting onto a casting drum whose surface temperature was controlled to 25°C to obtain a cast film. The amount of the ultraviolet absorber in the cast film was 1 part by mass relative to 100 parts by mass of PET.
[0465] The obtained cast film was heated with a roller set at 95°C, and then stretched 3.3 times in the flow direction while being heated by a radiation heater in such a manner that the film temperature at the 130mm point of the stretching section 400mm was 99°C and the film temperature at the 150mm point was 100°C, and then temporarily cooled to obtain a uniaxially stretched film. In the above-mentioned stretching section, the starting point is the stretching roller A and the end point is the stretching roller B, and the stretching rollers A and B each have two nip rollers. It should be noted that when heating with a radiation heater, turbulence is generated by blowing 80°C and 5m / s wind from the back of the radiation heater to the film, thereby disturbing the temperature uniformity of the film.
[0466] Next, both surfaces of the uniaxially stretched film were subjected to corona discharge treatment in air to set the wetting tension of the base film to 55 mN / m. Next, the following lubricating layer coating liquid was applied in-line to both corona discharge treated surfaces of the film to form a lubricating layer.
[0467] Next, the uniaxially stretched film is introduced into a tenter, preheated with hot air at 95°C, and then stretched 4.5 times in the width direction of the film at a temperature of 105°C in the first stage and 135°C in the second stage. Here, when the stretching interval in the width direction is divided into two parts, the stretching is performed in two stages in such a way that the stretching amount of the film at the midpoint of the stretching interval in the width direction is 80% of the stretching amount at the end of the stretching interval in the width direction. The above-mentioned "stretching amount" refers to the difference between the film width at the measurement location and the film width before stretching. For the film stretched in the width direction, a turbulent wind of about 55°C and 5m / s is blown from the inside and outside of the film for about 2 seconds, thereby cooling in a manner that the film temperature uniformity is disturbed. Next, heat treatment is performed using hot air in the tenter. The temperature of the hot air is increased in stages from 180°C to 245°C. Next, a 1% relaxation treatment is performed in the width direction under the same temperature conditions, and then a 1% relaxation treatment is performed in the width direction after being rapidly cooled to 100°C. Thereafter, the film was wound up to obtain a biaxially stretched polyester film as an optical plastic film of Example 1 having a width of more than 2100 mm.
[0468] <Slippery layer coating liquid>
[0469] A coating liquid containing a polyester resin having a glass transition temperature of 18° C., a polyester resin having a glass transition temperature of 82° C., and silica particles having an average particle size of 100 nm.
[0470] [Example 2]
[0471] A biaxially oriented polyester film as an optical plastic film of Example 2 was obtained in the same manner as in Example 1, except that the film temperature at the 130 mm point of the cast film was changed to 97°C, the film temperature at the 150 mm point was changed to 98°C, and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 60°C.
[0472] [Example 3]
[0473] A biaxially stretched polyester film as an optical plastic film of Example 3 was obtained in the same manner as in Example 2 except that the film temperature at a point 130 mm of the cast film was changed to 98°C.
[0474] [Example 4]
[0475] A biaxially oriented polyester film as an optical plastic film of Example 4 was obtained in the same manner as in Example 1, except that the film temperature at the 130 mm point of the cast film was changed to 98°C, the film temperature at the 150 mm point was changed to 105°C, the stretch ratio in the flow direction was changed to 3.9 times, and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 60°C.
[0476] [Example 5]
[0477] A biaxially oriented polyester film as an optical plastic film of Example 5 was obtained in the same manner as in Example 1, except that the film temperature at the 130 mm point of the cast film was changed to 98°C, the film temperature at the 150 mm point was changed to 105°C, the stretch ratio in the flow direction was changed to 4.1 times, and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 60°C.
[0478] [Example 6]
[0479] A biaxially stretched polyester film as an optical plastic film of Example 6 was obtained in the same manner as in Example 1, except that the film temperature at a point 130 mm of the cast film was changed to 98° C., the film temperature at a point 150 mm was changed to 110° C., the stretch ratio in the flow direction was changed to 3.5 times, the temperature of the wind blown from the back side of the radiation heater during stretching in the flow direction was changed to 90° C., and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 45° C.
[0480] [Example 7]
[0481] The film temperature at the 130 mm point of the cast film was changed to 95° C., the film temperature at the 150 mm point was changed to 99° C., the stretch ratio in the flow direction was changed to 3.1 times, the stretch ratio in the width direction was changed to 3.8 times, and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 45° C., a biaxially stretched polyester film as an optical plastic film of Example 7 was obtained in the same manner as in Example 1.
[0482] [Example 8]
[0483] A biaxially stretched polyester film as an optical plastic film of Example 8 was obtained in the same manner as in Example 1, except that the film temperature at a point 130 mm of the cast film was changed to 98°C, the stretch ratio in the flow direction was changed to 3.9 times, and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 55°C.
[0484] [Example 9]
[0485] A biaxially oriented polyester film as an optical plastic film of Example 9 was obtained in the same manner as in Example 1, except that the film temperature at the 130 mm point of the cast film was changed to 95°C, the film temperature at the 150 mm point was changed to 98°C, the stretch ratio in the flow direction was changed to 4.1 times, and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 60°C.
[0486] [Example 10]
[0487] A biaxially oriented polyester film as an optical plastic film of Example 10 was obtained in the same manner as in Example 1, except that the film temperature at the 130 mm point of the cast film was changed to 102°C, the film temperature at the 150 mm point was changed to 110°C, the stretch ratio in the flow direction was changed to 3.0 times, the stretch ratio in the width direction was changed to 3.2 times, and the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 40°C.
[0488] [Comparative Examples 1 to 5]
[0489] As an optical plastic film of a comparative example, the following plastic film was prepared.
[0490] <Comparative Example 1>
[0491] Triacetyl cellulose film (manufactured by Fujifilm, part number: TD40, thickness: 40 μm)
[0492] <Comparative Example 2>
[0493] Biaxially oriented polyester film (manufactured by Toyobo Co., Ltd., trade name: Cosmoshine A4300, thickness: 38 μm)
[0494] <Comparative Example 3>
[0495] Biaxially oriented polyester film (manufactured by Toray Industries, trade name: Lumiror 50U403, thickness: 50 μm)
[0496] <Comparative Example 4>
[0497] Biaxially oriented polyester film (manufactured by Mitsubishi Chemical Corporation, trade name: DIAFOIL T600, thickness: 23 μm)
[0498] <Comparative Example 5>
[0499] Uniaxially stretched polyester film (manufactured by Toyobo Co., Ltd., trade name: Cosmoshine TA048, thickness: 80 μm)
[0500] [Comparative Example 6]
[0501] The film temperature at the 130 mm point of the cast film was changed to 102° C., the film temperature at the 150 mm point was changed to 110° C., the stretch ratio in the flow direction was changed to 3.0 times, the stretch ratio in the width direction was changed to 3.2 times, the temperature of the wind containing turbulence blown to the film stretched in the width direction was changed to 65° C., and the air supply was changed not to be supplied from the back side of the radiation heater during stretching in the flow direction. A biaxially stretched polyester film as a plastic film for optics of Comparative Example 6 was obtained in the same manner as in Example 1.
[0502] 3. Fabrication of optical layered bodies
[0503] A coating liquid for forming a hard coat layer of the following formulation was applied to the optical plastic films of Examples 1 to 10 and Comparative Examples 1 to 6, dried, and irradiated with ultraviolet light to form a hard coat layer of 5 μm in thickness. Next, a coating liquid for forming a low refractive index layer of the following formulation was applied to the hard coat layer, dried, and irradiated with ultraviolet light to form a low refractive index layer of 100 nm in thickness and a refractive index of 1.30, thereby obtaining optical layered bodies of Examples 1 to 10 and Comparative Examples 1 to 6.
[0504] <Hard Coat Layer Forming Coating Liquid>
[0505] · 25.1 parts by mass of UV curable compound
[0506] (Acrylic polymer, manufactured by Daesung Fine Chemicals Co., Ltd., trade name 8KX-077)
[0507] · 25.4 parts by mass of UV curable compound
[0508] (Multifunctional acrylate, manufactured by Nippon Kayaku Co., Ltd., trade name PET-30)
[0509] · Photopolymerization initiator 1.0 parts by mass
[0510] (IGM Resins BV, trade name "Omnirad 184")
[0511] ·Silicone leveling agent 0.30 parts by mass
[0512] (Momentive Performance Materials, trade name TSF4460)
[0513] · Dilution solvent 37.4 parts by mass
[0514] (Mixed solvent of toluene, IPA and PMA in a mass ratio of 47:33:20)
[0515] <Coating liquid for forming low refractive index layer>
[0516] · 0.6 parts by mass of UV curable compound
[0517] (Trifunctional or higher but tetrafunctional alkoxylated pentaerythritol acrylate, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., trade name "NK ESTER ATM-4PL")
[0518] · Photopolymerization initiator 0.1 parts by mass
[0519] (IGM Resins BV, trade name "Omnirad 127")
[0520] Hollow silica 1.88 parts by mass
[0521] (average particle size 60nm)
[0522] Solid silica 0.3 parts by mass
[0523] (Average particle size 12nm)
[0524] · Fluorine-based antifouling agent 1.16 parts by mass
[0525] (DIC Corporation, trade name "MEGAFACE F-568")
[0526] 92.7 parts by mass of dilution solvent (a mixed solvent of methyl isobutyl ketone and propylene glycol monomethyl ether acetate in a mass ratio of 90:10)
[0527]
[0528] In Tables 1 and 2, Ratio 1 to Ratio 5 refer to the following ratios.
[0529] Ratio 1: Ratio of small samples with an average in-plane retardation value of 50 nm or more and 1200 nm or less
[0530] Ratio 2: Ratio of small samples with a standard deviation σ of the slow axis angle of 0.8 degrees or more
[0531] Ratio 3: Ratio of small samples with a retardation of 2000nm or more in the thickness direction
[0532] Ratio 4: Ratio of small samples with a ratio of average in-plane phase difference / thickness direction phase difference of 0.20 or less
[0533] Ratio 5: E 0-20 The proportion of small samples with a size of 1.4 μm / g or more
[0534] In addition, in Tables 1 to 3, S1 represents sample 1, S2 represents sample 2, S3 represents sample 3, and S4 represents sample 4.
[0535]
[0536] [Table 3]
[0537] Table 3
[0538]
[0539] From the results in Tables 1 to 3, it can be confirmed that the optical plastic film of the embodiment can suppress rainbow spots when observed with the naked eye and black screens when observed with polarized sunglasses without increasing the in-plane phase difference and without requiring axis alignment. In addition, it can be confirmed that the optical plastic film of the embodiment can suppress the remaining bending marks or cracks after the bending test regardless of the bending direction.
[0540] In addition, it was confirmed that the optical plastic films of the examples had good pencil hardness because they satisfied the erosion rate of condition 5. In particular, it was confirmed that the optical plastic films of Examples 1 to 3, Sample 2 of Example 4, Samples 1 to 2 of Example 5, and Examples 8 to 9 had extremely good pencil hardness because the proportion of small samples satisfying the erosion rate of condition 5 was 90% or more and the angle σ of the slow axis of condition 2 was not too large. The erosion rate of condition 5 is considered to mainly improve the strength in the thickness direction. Therefore, it is considered that the optical plastic films of the examples satisfying the erosion rate of condition 5 can improve the pencil hardness. Among them, when the proportion of small samples satisfying the erosion rate of condition 5 is 90% or more, the pencil hardness can be easily improved further. In addition, in the examples, the optical plastic films of Examples 1 to 5 and 8 to 9 had good in-plane orientation because the angle σ of the slow axis of condition 2 was not too large. That is, the optical plastic films of Examples 1 to 5 and 8 to 9 having good in-plane orientation have little in-plane property deviation, so it is considered that the reduction of pencil hardness starting from a part with local weak strength can be easily suppressed. From this, it is considered that in the examples, the optical plastic films of Examples 1 to 3, Sample 2 of Example 4, Samples 1 and 2 of Example 5, and Examples 8 and 9 can have extremely good pencil hardness.
[0541] Although not described in the table, the plastic films of Examples 1 to 10 satisfy Condition 6 described in the specification. Therefore, it can be said that the plastic films of Examples 1 to 10 are excellent in film homogeneity in the thickness direction and good in coating suitability.
[0542] Explanation of symbols
[0543] 10: Plastic film for optics
[0544] 10a: Sheet plastic film
[0545] 10b: Rolled plastic film
[0546] 20: Display components
[0547] 30: Polarizer
[0548] 31: Polarization element
[0549] 32: First transparent protective plate
[0550] 33: Second transparent protective plate
[0551] 40: Optical layered body
[0552] 41: Hard coating
[0553] 42: Anti-reflective layer
[0554] 100: Image display device
[0555] 110: Container
[0556] 120: Receiver
[0557] 210: Test fluid piping
[0558] 220: Compressed air piping
[0559] 230: Return piping
[0560] 310, 320: Flow meter
[0561] 410, 420: Pressure gauge
[0562] 500: Jet
[0563] 510: Nozzle
[0564] 520: Shell
[0565] 600: Cross-section profile acquisition unit
[0566] 810: Sample mounting table
[0567] 820: Support
[0568] 900: Erosion rate measuring device
[0569] A1: water
[0570] A2: Spherical silica
[0571] A3: Air
[0572] A4: Worn plastic film.
Claims
1. An optical plastic film, which satisfies the following conditions 1 and 2, <Condition 1> A large sample of 200 mm × 300 mm in size is cut out from a plastic film; the large sample is divided into 30 small samples of 40 mm × 50 mm; a 30 mm × 40 mm area after removing 5 mm from the edge of each small sample is subdivided into more than 47,000 areas, and then the in-plane phase difference of each of the subdivided areas is measured; among the 30 small samples, the proportion of small samples showing an average in-plane phase difference of more than 300 nm and less than 950 nm is more than 70%; <Condition 2> For the 30 small samples, the angle of the slow axis of each area after each small sample was subdivided was measured in the same manner as in condition 1; among the 30 small samples, the standard deviation σ calculated from the angle of the slow axis of each measured area showed that the proportion of small samples with an angle of more than 0.8 degrees and less than 20.0 degrees was more than 70%.
2. The optical plastic film according to claim 1, wherein In the condition 1, among the 30 small samples, the proportion of small samples in which the average value of the in-plane phase difference of each measurement area is 300 nm or more and 950 nm or less is 100%. In the condition 2, among the 30 small samples, the proportion of small samples having a standard deviation σ calculated from the angle of the slow axis of each measurement region of 0.8 degrees or more and 20.0 degrees or less was 100%.
3. The optical plastic film according to claim 1 or 2, further satisfying the following condition 3: <Condition 3> For the 30 small samples, the phase difference in the thickness direction was measured at the center of the 30 mm×40 mm area. Among the 30 small samples, the proportion of small samples showing a phase difference in the thickness direction of 2000 nm or more was 50% or more.
4. The optical plastic film according to claim 3, further satisfying the following condition 4: <Condition 4> Among the 30 small samples, the proportion of small samples in which the average value of the in-plane phase difference relative to the phase difference in the thickness direction was 0.20 or less was 50% or more. 5 . An optical layered body comprising the optical plastic film according to claim 1 and a functional layer thereon. The optical layered body according to claim 5 , comprising an antireflection layer as the functional layer.
7. A polarizing plate comprising a polarizing element, a first transparent protective plate disposed on one side of the polarizing element, and a second transparent protective plate disposed on the other side of the polarizing element, wherein: At least one of the first transparent protective plate and the second transparent protective plate includes the optical plastic film according to any one of claims 1 to 4.
8. An image display device comprising a display element and a plastic film disposed on a light emitting surface side of the display element, wherein: The plastic film is the optical plastic film according to any one of claims 1 to 4. 9 . The image display device according to claim 8 , further comprising a polarizing element between the display element and the plastic film.
Citation Information
Patent Citations
Polarizing plate and liquid crystal panel
JP2009300611A
Polarizing plate
JP2010244059A
Visibility improving method of liquid crystal display device, and liquid crystal display device using the same
JP2011107198A
Optical laminate, polarizing plate and display device
CN109782379A
Film for polarizer supporting base material
JP2011053271A